Adhesion GPCR Gpr126 (Adgrg6) Expression Profiling in Zebrafish, Mouse, and Human Kidney. - Cazorla-Vázquez, Salvador; Kösters, Peter; Bertz, Simone; Pfister, Frederick; Daniel, Christoph; Dedden, Mark; Zundler, Sebastian; Jobst-Schwan, Tilman; Amann, Kerstin Ute; Engel, Felix (Cells, 2023)
Adhesion G protein-coupled receptors (aGPCRs) comprise the second-largest class of GPCRs, the most common target for approved pharmacological therapies. aGPCRs play an important role in development and disease and have recently been associated with the kidney. Several aGPCRs are expressed in the kidney and some aGPCRs are either required for kidney development or their expression level is altered in diseased kidneys. Yet, general aGPCR function and their physiological role in the kidney are poorly understood. Here, we characterize in detail Gpr126 (Adgrg6) expression based on RNAscope® technology in zebrafish, mice, and humans during kidney development in adults. Gpr126 expression is enriched in the epithelial linage during nephrogenesis and persists in the adult kidney in parietal epithelial cells, collecting ducts, and urothelium. Single-cell RNAseq analysis shows that gpr126 expression is detected in zebrafish in a distinct ionocyte sub-population. It is co-detected selectively with slc9a3.2, slc4a4a, and trpv6, known to be involved in apical acid secretion, buffering blood or intracellular pH, and to maintain high cytoplasmic Ca2+ concentration, respectively. Furthermore, gpr126-expressing cells were enriched in the expression of potassium transporter kcnj1a.1 and gcm2, which regulate the expression of a calcium sensor receptor. Notably, the expression patterns of Trpv6, Kcnj1a.1, and Gpr126 in mouse kidneys are highly similar. Collectively, our approach permits a detailed insight into the spatio-temporal expression of Gpr126 and provides a basis to elucidate a possible role of Gpr126 in kidney physiology.
EVALuna2:539836
Keywords: adhesion GPCR; kidney development; Gpr126; parietal epithelial cell; collecting duct; urothelium; ionocytes; zebrafish; RNAscope

Adhesion GPCRs in Kidney Development and Disease - Cazorla-Vázquez, Salvador; Engel, Felix (Frontiers in Cell and Developmental Biology, 2018)
Chronic kidney disease (CKD) represents the fastest growing pathology worldwide with a prevalence of >10% in many countries. In addition, kidney cancer represents 5% of all new diagnosed cancers. As currently no effective therapies exist to restore kidney function after CKD- as well as cancer-induced renal damage, it is important to elucidate new regulators of kidney development and disease as new therapeutic targets. G protein-coupled receptors (GPCRs) represent the most successful class of pharmaceutical targets. In recent years adhesion GPCRs (aGPCRs), the second largest GPCR family, gained significant attention as they are present on almost all mammalian cells, are associated to a plethora of diseases and regulate important cellular processes. aGPCRs regulate for example cell polarity, mitotic spindle orientation, cell migration, and cell aggregation; all processes that play important roles in kidney development and/or disease. Moreover, polycystin-1, a major regulator of kidney development and disease, contains a GAIN domain, which is otherwise only found in aGPCRs. In this review, we assess the potential of aGPCRs as therapeutic targets for kidney disease. For this purpose we have summarized the available literature and analyzed data from the databases The Human Protein Atlas, EURExpress, Nephroseq, FireBrowse, cBioPortal for Cancer Genomics and the National Cancer Institute Genomic Data Commons data portal (NCIGDC). Our data indicate that most aGPCRs are expressed in different spatio-temporal patterns during kidney development and that altered aGPCR expression is associated with a variety of kidney diseases including CKD, diabetic nephropathy, lupus nephritis as well as renal cell carcinoma. We conclude that aGPCRs present a promising new class of therapeutic targets and/or might be useful as diagnostic markers in kidney disease.
EVALuna2:34820

Adhesion G Protein-Coupled Receptor Gpr126 (Adgrg6) Expression Profiling in Diseased Mouse, Rat, and Human Kidneys - Kösters, Peter; Cazorla Vázquez, Salvador; Krüger, René; Daniel, Christoph; Vonbrunn, Eva; Amann, Kerstin Ute; Engel, Felix (Cells, 2024)
Uncovering the function of understudied G protein-coupled receptors (GPCRs) provides a wealth of untapped therapeutic potential. The poorly understood adhesion GPCR Gpr126 (Adgrg6) is widely expressed in developing kidneys. In adulthood, Gpr126 expression is enriched in parietal epithelial cells (PECs) and epithelial cells of the collecting duct and urothelium. Whether Gpr126 plays a role in kidney disease remains unclear. Here, we characterized Gpr126 expression in diseased kidneys in mice, rats, and humans. RT-PCR data show that Gpr126 expression is altered in kidney disease. A quantitative RNAscope® analysis utilizing cell type-specific markers revealed that Gpr126 expression upon tubular damage is mainly increased in cell types expressing Gpr126 under healthy conditions as well as in cells of the distal and proximal tubules. Upon glomerular damage, an increase was mainly detected in PECs. Notably, Gpr126 expression was upregulated in an ischemia/reperfusion model within hours, while upregulation in a glomerular damage model was only detected after weeks. An analysis of kidney microarray data from patients with lupus nephritis, IgA nephropathy, focal segmental glomerulosclerosis (FSGS), hypertension, and diabetes as well as single-cell RNA-seq data from kidneys of patients with acute kidney injury and chronic kidney disease indicates that GPR126 expression is also altered in human kidney disease. In patients with FSGS, an RNAscope® analysis showed that GPR126 mRNA is upregulated in PECs belonging to FSGS lesions and proximal tubules. Collectively, we provide detailed insights into Gpr126 expression in kidney disease, indicating that GPR126 is a potential therapeutic target.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adhesion GPCR; collecting duct; focal segmental glomerulosclerosis; Gpr126; human; kidney disease; parietal epithelial cell; RNAscope; urothelium

Advances in heart regeneration based on cardiomyocyte proliferation and regenerative potential of binucleated cardiomyocytes and polyploidization - Leone, Marina; Engel, Felix (Clinical Science, 2019)
One great achievement in medical practice is the reduction in acute mortality of myocardial infarction due to identifying risk factors, antiplatelet therapy, optimized hospitalization and acute percutaneous coronary intervention. Yet, the prevalence of heart failure is increasing presenting a major socio-economic burden. Thus, there is a great need for novel therapies that can reverse damage inflicted to the heart. In recent years, data have accumulated suggesting that induction of cardiomyocyte proliferation might be a future option for cardiac regeneration. Here, we review the relevant literature since September 2015 concluding that it remains a challenge to verify that a therapy induces indeed cardiomyocyte proliferation. Most importantly, it is unclear that the detected increase in cardiomyocyte cell cycle activity is required for an associated improved function. In addition, we review the literature regarding the evidence that binucleated and polyploid mononucleated cardiomyocytes can divide, and put this in context to other cell types. Our analysis shows that there is significant evidence that binucleated cardiomyocytes can divide. Yet, it remains elusive whether also polyploid mononucleated cardiomyocytes can divide, how efficient proliferation of binucleated cardiomyocytes can be induced, what mechanism regulates cell cycle progression in these cells, and what fate and physiological properties the daughter cells have. In summary, we propose to standardize and independently validate cardiac regeneration studies, encourage the field to study the proliferative potential of binucleated and polyploid mononucleated cardiomyocytes, and to determine whether induction of polyploidization can enhance cardiac function post-injury.
CRIS-Team Scopus Importer:2019-06-28
Keywords: binucleation; cell cycle; heart regeneration; polyploidy; proliferation

A large-scale functional high-throughput screening identifies miR-515 and miR-519e as potent inducers of human iPSC-cardiomyocyte proliferation - Renikunta, H. V.; Lazarow, K.; Gong, Y.; Shukla, P. C.; Giral, H.; Kratzer, A.; Nageswaran, V.; Opitz, L.; Engel, Felix; Haghikia, A.; Paneni, F.; Von Kries, J. P.; et al. (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Alternative splicing of pericentrin contributes to cell cycle control in cardiomyocytes - Steinfeldt, Jakob; Becker, Robert; Vergarajauregui, Silvia; Engel, Felix (Journal of Cardiovascular Development and Disease, 2021)
Induction of cardiomyocyte proliferation is a promising option to regenerate the heart. Thus, it is important to elucidate mechanisms that contribute to the cell cycle arrest of mammalian cardiomyocytes. Here, we assessed the contribution of the pericentrin (Pcnt) S isoform to cell cycle arrest in postnatal cardiomyocytes. Immunofluorescence staining of Pcnt isoforms combined with SiRNA-mediated depletion indicates that Pcnt S preferentially localizes to the nuclear envelope, while the Pcnt B isoform is enriched at centrosomes. This is further supported by the localization of ectopically expressed FLAG-tagged Pcnt S and Pcnt B in postnatal cardiomyocytes. Analysis of centriole configuration upon Pcnt depletion revealed that Pcnt B but not Pcnt S is required for centriole cohesion. Importantly, ectopic expression of Pcnt S induced centriole splitting in a heterologous system, ARPE-19 cells, and was sufficient to impair DNA synthesis in C2C12 myoblasts. Moreover, Pcnt S depletion enhanced serum-induced cell cycle re-entry in postnatal cardiomyocytes. Analysis of mitosis, binucleation rate, and cell number suggests that Pcnt S depletion enhances serum-induced progression of postnatal cardiomyocytes through the cell cycle resulting in cell division. Collectively, our data indicate that alternative splicing of Pcnt contributes to the establishment of cardiomyocyte cell cycle arrest shortly after birth.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cardiomyocyte; Cell cycle; Centriole splitting; Centrosome; Heart regeneration; Non-centrosomal microtubule organizing center; Pericentrin

Author Correction: Non-professional phagocytosis: a general feature of normal tissue cells (Scientific Reports, (2019), 9, 1, (11875), 10.1038/s41598-019-48370-3) - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-06-16

A VERSATILE MODEL OF CARDIAC TISSUE FROM HIPSC-DERIVED CARDIOMYOCYTES WITHIN PERICARDIAL MATRIX HYDROGELS DOPED WITH HYDRAZIDE FUNCTIONALIZED MWCNTS FOR PHARMACEUTICAL SCREENING AND TISSUE ENGINEERING APPLICATIONS - Roshanbinfar, Kaveh; Oommen, Oommen Podiyan; Hilborn, Jons; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

BIOHYBRID HYDROGEL WITH ENHANCED ELECTROCONDUCTIVITY ADVANCES MATURATION OF HIPSC-DERIVED CARDIOMYOCYTES - Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Biomimetic Organic-Inorganic Nanocomposite Scaffolds to Regenerate Cranial Bone Defects in a Rat Animal Model - Moosavifar, Mirjavad; Parsaei, Houman; Hosseini, Seyedjamal; Mirmontazeri, Seyed Mohammad; Ahadi, Reza; Ahadian, Samad; Engel, Felix; Roshanbinfar, Kaveh (ACS Biomaterials Science and Engineering, 2022)
While bone regenerates itself after an injury, a critical bone defect requires external interventions. Engineering approaches to restore bone provide a temporary scaffold to support the damage and provide beneficial biological cues for bone repair. Biomimetically generated scaffolds replicate the naturally occurring phenomena in bone regeneration. In this study, a gelatin-calcium phosphate nanocomposite was synthesized by an efficient and cost-effective double-diffusion biomimetic approach. Calcium and phosphate ions are impregnated in the gelatin, mimicking the natural bone mineralization process. Glutaraldehyde from 0.5 to 2 w/v% was used for gelatin cross-linking and mechanical properties of the scaffold, and its biological support for rat bone marrow mesenchymal stromal cells was analyzed. Analysis of scanning electron microscopy images of the nanocomposite scaffolds and Fourier transform infrared (FTIR) and X-ray diffraction (XRD) characterizations of these scaffolds confirmed precipitation of calcium phosphates in the gelatin. Moreover, lysozyme degradation assay showed that scaffold degradation reversely correlates with the concentration of the cross-linking agent. Increased glutaraldehyde concentrations enhanced the mechanical properties of the scaffolds, bringing them closer to those of cancellous bone. Rat bone marrow mesenchymal stromal cells maintained their viability on these scaffolds compared to standard cell culture plates. In addition, these cells showed differentiation into bone lineage as evaluated from alkaline phosphatase activity up to 21 days and Alizarin red staining of the cells over 28 days. Eventually, scaffolds were implanted in a cranial defect in a rat animal model with a 5 mm diameter. Bone regeneration was studied over 90 days. Analysis of histological sections of the injury and computer tomography images revealed that nanocomposite scaffolds cross-linked with 1% w/v glutaraldehyde provide the maximum bone regeneration after 90 days. Collectively, our data show that nanocomposite scaffolds developed here provide effective regeneration for extensive bone defects in vivo.
CRIS-Team Scopus Importer:2022-04-15
Keywords: biomimetic scaffold; bone tissue engineering; gelatin-calcium phosphate; nanocomposite graft

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

Carbon nanotube doped pericardial matrix derived electroconductive biohybrid hydrogel for cardiac tissue engineering - Roshanbinfar, Kaveh; Mohammadi, Zahra; Sheikh-Mahdi Mesgar, Abdorreza; Dehghan, Mohammad Mehdi; Oommen, Oommen P.; Hilborn, Jöns; Engel, Felix (Biomaterials Science, 2019)
Cardiovascular diseases represent a major socio-economic burden. In recent years, considerable effort has been invested in optimizing cell delivery strategies to advance cell transplantation therapies to restore heart function for example after an infarct. A particular issue is that the implantation of cells using a non-electroconductive matrix potentially causes arrhythmia. Here, we demonstrate that our hydrazide-functionalized nanotubes-pericardial matrix-derived electroconductive biohybrid hydrogel provides a suitable environment for maturation of human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. hiPSC-derived cardiomyocytes exhibited an improved contraction amplitude (>500%) on conductive hydrogels compared to cells cultured on Matrigel®. This was accompanied by increased cellular alignment, enhanced connexin 43 expression, and improved sarcomere organization suggesting maturation of the hiPSC-derived cardiomyocytes. Sarcomeric length of these cells increased from 1.3 to 1.7 μm. Moreover, 3D cell-laden engineered tissues exhibited enhanced calcium handling as well as positive response to external electrical and pharmaceutical stimulation. Collectively, our data indicate that our biohybrid hydrogels consisting of solubilized nanostructured pericardial matrix and electroconductive positively charged hydrazide-conjugated carbon nanotubes provide a promising material for stem cell-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-09-03

Cardiac injury of the newborn mammalian heart accelerates cardiomyocyte terminal differentiation - Zebrowski, David; Jensen, Charlotte H.; Becker, Robert; Ferrazzi, Fulvia; Baun, Christina; Hvidsten, Svend; Sheikh, Soren P.; Polizzotti, Brian D.; Andersen, Ditte C.; Engel, Felix (Scientific Reports, 2017)
After birth cardiomyocytes undergo terminal differentiation, characterized by binucleation and centrosome disassembly, rendering the heart unable to regenerate. Yet, it has been suggested that newborn mammals regenerate their hearts after apical resection by cardiomyocyte proliferation. Thus, we tested the hypothesis that apical resection either inhibits, delays, or reverses cardiomyocyte centrosome disassembly and binucleation. Our data show that apical resection rather transiently accelerates centrosome disassembly as well as the rate of binucleation. Consistent with the nearly 2-fold increased rate of binucleation there was a nearly 2-fold increase in the number of cardiomyocytes in mitosis indicating that the majority of injury-induced cardiomyocyte cell cycle activity results in binucleation, not proliferation. Concurrently, cardiomyocytes undergoing cytokinesis from embryonic hearts exhibited midbody formation consistent with successful abscission, whereas those from 3 day-old cardiomyocytes after apical resection exhibited midbody formation consistent with abscission failure. Lastly, injured hearts failed to fully regenerate as evidenced by persistent scarring and reduced wall motion. Collectively, these data suggest that should a regenerative program exist in the newborn mammalian heart, it is quickly curtailed by developmental mechanisms that render cardiomyocytes post-mitotic.
EVALuna2:9380

Cardiomyocyte binucleation is associated with aberrant mitotic microtubule distribution, mislocalization of RhoA and IQGAP3, as well as defective actomyosin ring anchorage and cleavage furrow ingression - Leone, Marina; Musa, Gentian; Engel, Felix (Cardiovascular Research, 2018)
Aims After birth mammalian cardiomyocytes initiate a last cell cycle which results in binucleation due to cytokinesis failure. Despite its importance for cardiac regenerative therapies, this process is poorly understood. Here, we aimed at a better understanding of the difference between cardiomyocyte proliferation and binucleation and providing a new tool to distinguish these two processes.Methods and results Monitoring of cell division by time-lapse imaging revealed that rat cardiomyocyte binucleation stems from a failure to properly ingress the cleavage furrow. Astral microtubule required for actomyosin ring anchorage and thus furrow ingression were not symmetrically distributed at the periphery of the equatorial region during anaphase in binucleating cardiomyocytes. Consequently, RhoA, the master regulator of actomyosin ring formation and constriction, non-muscle myosin IIB, a central component of the actomyosin ring, as well as IQGAP3 were abnormally localized during cytokinesis. In agreement with improper furrow ingression, binucleation in vitro and in vivo was associated with a failure of RhoA and IQGAP3 to localize to the stembody of the midbody.Conclusion Taken together, these results indicate that naturally occurring cytokinesis failure in primary cardiomyocytes is due to an aberrant mitotic microtubule apparatus resulting in inefficient anchorage of the actomyosin ring to the plasma cell membrane. Thus, cardiomyocyte binucleation and division can be discriminated by the analysis of RhoA as well as IQGAP3 localization.
Keywords: IQGAP3; RhoA; Actomyosin ring; Cardiomyocytes; Microtubules

Cardiomyocyte Cell-Cycle Activity during Preadolescence - Soonpaa, Mark H.; Zebrowski, David; Platt, Colin; Rosenzweig, Anthony; Engel, Felix; Field, Loren J. (Cell, 2015)
EVALuna2:25501

Cardiomyocyte proliferation in cardiac development and regeneration: a guide to methodologies and interpretations - Leone, Marina; Magadum, Ajit; Engel, Felix (American Journal of Physiology-Heart and Circulatory Physiology, 2015)
The newt and the zebrafish have the ability to regenerate many of their tissues and organs including the heart. Thus, a major goal in experimental medicine is to elucidate the molecular mechanisms underlying the regenerative capacity of these species. A wide variety of experiments have demonstrated that naturally occurring heart regeneration relies on cardiomyocyte proliferation. Thus, major efforts have been invested to induce proliferation of mammalian cardiomyocytes in order to improve cardiac function after injury or to protect the heart from further functional deterioration. In this review, we describe and analyze methods currently used to evaluate cardiomyocyte proliferation. In addition, we summarize the literature on naturally occurring heart regeneration. Our analysis highlights that newt and zebrafish heart regeneration relies on factors that are also utilized in cardiomyocyte proliferation during mammalian fetal development. Most of these factors have, however, failed to induce adult mammalian cardiomyocyte proliferation. Finally, our analysis of mammalian neonatal heart regeneration indicates experiments that could resolve conflicting results in the literature, such as binucleation assays and clonal analysis. Collectively, cardiac regeneration based on cardiomyocyte proliferation is a promising approach for improving adult human cardiac function after injury, but it is important to elucidate the mechanisms arresting mammalian cardiomyocyte proliferation after birth and to utilize better assays to determine formation of new muscle mass.
EVALuna2:25502

Changes in glomerular parietal epithelial cells in mouse kidneys with advanced age - Roeder, Sebastian S.; Stefanska, Ania; Eng, Diana G.; Kaverina, Natalya; Sunseri, Maria W.; Mcnicholas, Bairbre A.; Rabinovitch, Peter; Engel, Felix; Daniel, Christoph; Amann, Kerstin Ute; Lichtnekert, Julia; Pippin, Jeffrey W.; et al. (American Journal of Physiology-Renal Physiology, 2015)
Kidney aging is accompanied by characteristic changes in the glomerulus, but little is known about the effect of aging on glomerular parietal epithelial cells (PECs), nor if the characteristic glomerular changes in humans and rats also occur in very old mice. Accordingly, a descriptive analysis was undertaken in 27-mo-old C57B6 mice, considered advanced age. PEC density was significantly lower in older mice compared with young mice (aged 3 mo), and the decrease was more pronounced in juxtamedullary glomeruli compared with outer cortical glomeruli. In addition to segmental and global glomerulosclerosis in older mice, staining for matrix proteins collagen type IV and heparan sulfate proteoglycan were markedly increased in Bowman's capsules of older mouse glomeruli, consistent with increased extracellular matrix production by PECs. De novo staining for CD44, a marker of activated and profibrotic PECs, was significantly increased in aged glomeruli. CD44 staining was more pronounced in the juxtamedullary region and colocalized with phosphorylated ERK. Additionally, a subset of aged PECs de novo expressed the epithelial-to-mesenchymal transition markers ?-smooth muscle and vimentin, with no changes in epithelial-to-mesenchymal transition markers E-cadherin and ?-catenin. The mural cell markers neural/glial antigen 2, PDGF receptor-?, and CD146 as well as Notch 3 were also substantially increased in aged PECs. These data show that mice can be used to better understand the aging kidney and that PECs undergo substantial changes, especially in juxtamedullary glomeruli, that may participate in the overall decline in glomerular structure and function with advancing age.
EVALuna2:25490

CHIR99021 Promotes hiPSC-Derived Cardiomyocyte Proliferation in Engineered 3D Microtissues - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (Advanced Healthcare Materials, 2021)
Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modeling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Here, it is shown that the integration of the glycogen synthase kinase-3β inhibitor CHIR99021 in collagen I hydrogels promotes proliferation of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered 3D cardiac microtissues. CHIR99021 has no effect on the gelation kinetics or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ≈2-fold within 7 d post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 d in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increased speed of contraction and contraction amplitude, and reduced peak-to-peak time. The CHIR99021-stimulated engineered cardiac microtissues exhibit spontaneous rhythmic contractions for at least 35 d. Collectively, the data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac microtissues by increasing cardiomyocyte density.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiomyocytes; CHIR99021; heart; hiPSC; proliferation; tissue engineering

Collagen Hydrogel Containing Polyethylenimine-Gold Nanoparticles for Drug Release and Enhanced Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Kolesnik-Gray, Maria; Angeloni, Miriam; Schrüfer, Stefan; Fiedler, Maren; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Engel, Felix (Advanced Healthcare Materials, 2023)
Cardiac tissue engineering is a promising strategy to prevent heart failure. However, several issues remain unsolved, including efficient electrical coupling and incorporating factors to enhance tissue maturation and vascularization. Herein, a biohybrid hydrogel that enhances beating properties of engineered cardiac tissues and allows drug release concurrently is developed. Gold nanoparticles (AuNPs) with different sizes (18–241 nm) and surface charges (33.9–55.4 mV) are synthesized by reducing gold (III) chloride trihydrate using branched polyethyleneimine (bPEI). These nanoparticles increase gel stiffness from ≈91 to ≈146 kPa, enhance electrical conductivity of collagen hydrogels from ≈40 to 49–68 mS cm−1, and allow slow and steady release of loaded drugs. Engineered cardiac tissues based on bPEI-AuNP-collagen hydrogels and either primary or human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes show enhanced beating properties. hiPSC-derived cardiomyocytes exhibit more aligned and wider sarcomeres in bPEI-AuNP-collagen hydrogels compared to collagen hydrogels. Furthermore, the presence of bPEI-AuNPs result in advanced electrical coupling evidenced by synchronous and homogenous calcium flux throughout the tissue. RNA-seq analyses are in agreement with these observations. Collectively, this data demonstrate the potential of bPEI-AuNP-collagen hydrogels to improve tissue engineering approaches to prevent heart failure and possibly treat diseases of other electrically sensitive tissues.
CRIS-Team Scopus Importer:2023-04-21
Keywords: collagen; gold nanoparticles; heart; tissue engineering

CRISPR-mediated fluorescent tagging of endogenous PCM1 enables live cell imaging of non-centrosomal MTOC formation in muscle cells - Becker, Robert; Engel, Felix (2018)
EVALuna2:34442

Deletion of Gas2l3 in mice leads to specific defects in cardiomyocyte cytokinesis during development - Stopp, Sabine; Gruendl, Marco; Fackler, Marc; Malkmus, Jonas; Leone, Marina; Naumann, Ronald; Frantz, Stefan; Wolf, Elmar; Von Eyss, Bjoern; Engel, Felix; Gaubatz, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2017)
GAS2L3 is a recently identified cytoskeleton-associated protein that interacts with actin filaments and tubulin. The in vivo function of GAS2L3 in mammals remains unknown. Here, we show that mice deficient in GAS2L3 die shortly after birth because of heart failure. Mammalian cardiomyocytes lose the ability to proliferate shortly after birth, and further increase in cardiac mass is achieved by hypertrophy. The proliferation arrest of cardiomyocytes is accompanied by binucleation through incomplete cytokinesis. We observed that GAS2L3 deficiency leads to inhibition of cardiomyocyte proliferation and to cardiomyocyte hypertrophy during embryonic development. Cardiomyocyte-specific deletion of GAS2L3 confirmed that the phenotype results from the loss of GAS2L3 in cardiomyocytes. Cardiomyocytes from Gas2l3-deficient mice exhibit increased expression of a p53-transcriptional program including the cell cycle inhibitor p21. Furthermore, loss of GAS2L3 results in premature binucleation of cardiomyocytes accompanied by unresolved midbody structures. Together these results suggest that GAS2L3 plays a specific role in cardiomyocyte cytokinesis and proliferation during heart development.
EVALuna2:25556

Designing of spider silk proteins for human induced pluripotent stem cell-based cardiac tissue engineering - Esser, Tilman; Trossmann, Vanessa T.; Lentz, Sarah; Engel, Felix; Scheibel, T (Materials Today Bio, 2021)
Materials made of recombinant spider silk proteins are promising candidates for cardiac tissue engineering, and their suitability has so far been investigated utilizing primary rat cardiomyocytes. Herein, we expanded the tool box of available spider silk variants and demonstrated for the first time that human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes attach, contract, and respond to pharmacological treatment using phenylephrine and verapamil on explicit spider silk films. The hiPSC-cardiomyocytes contracted for at least 14 days on films made of positively charged engineered Araneus diadematus fibroin 4 (eADF4(κ16)) and three different arginyl-glycyl-aspartic acid (RGD)-tagged spider silk variants (positively or negatively charged and uncharged). Notably, hiPSC-cardiomyocytes exhibited different morphologies depending on the spider silk variant used, with less spreading and being smaller on films made of eADF4(κ16) than on RGD-tagged spider silk films. These results indicate that spider silk engineering is a powerful tool to provide new materials suitable for hiPSC-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2021-06-25

DEVELOPMENT OF APPROACHES FOR A TWO-LAYER PATCH COMBINING ELECTROSPINNING AND 3D PRINTING WITH IMPROVED ELECTRICAL STIMULUS TRANSMISSION AND SELF-REGULATING VISCOELASTIC PROPERTIES FOR APPLICATION IN CARDIAC TISSUE ENGINEERING - Boccaccini, Aldo R.; Vogt, Lena; Ruther, Florian; Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Direct 3D‐Bioprinting of hiPSC‐derived Cardiomyocytes to Generate Functional Cardiac Tissues - Esser, Tilman; Anspach, Annalise; Muenzebrock, Katrin; Kah, Delf-Thorge Eric; Schrüfer, Stefan; Schenk, Joachim; Heinze, Katrin G.; Schubert, Dirk W.; Fabry, Ben; Engel, Felix (Advanced Materials, 2023)
3D-bioprinting is a promising technology to produce human tissues as drug screening tool or for organ repair. However, direct printing of living cells has proven difficult. Here, we present a method to directly 3D-bioprint human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes embedded in a collagen-hyaluronic acid ink generating centimeter-sized functional ring- and ventricle-shaped cardiac tissues in an accurate and reproducible manner. The printed tissues contained hiPSC-derived cardiomyocytes with well-organized sarcomeres and exhibited spontaneous and regular contractions, which persisted for several months and were able to contract against passive resistance. Importantly, beating frequencies of the printed cardiac tissues could be modulated by pharmacological stimulation. This approach opens up new possibilities for generating complex functional cardiac tissues as models for advanced drug screening or as tissue grafts for organ repair or replacement.<br

Direct 3D printing of hiPSC-cardiomyocytes in collagen-based bioinks - Esser, Tilman; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Editorial: Methods in cardiovascular biologics and regenerative medicine - Gurusamy, Narasimman; Bergmann, Olaf; Castaldo, Clotilde; Huang, Ngan F.; Lien, Ching Ling; Tan, Jun Jie; Engel, Felix (Frontiers in Cardiovascular Medicine, 2024)
CRIS-Team Scopus Importer:2024-10-04
Keywords: 3D-bioprinting; cardiac remuscularization; methods in cardiovascular biologics; mitochondrial function; pericytes; regenerative medicine; tissue engineering; vascular grafts

Electrically Conductive Collagen-PEDOT:PSS Hydrogel Prevents Post-Infarct Cardiac Arrhythmia and Supports hiPSC-Cardiomyocyte Function - Roshanbinfar, Kaveh; Schiffer, Miriam; Carls, Esther; Angeloni, Miriam; Kolesnik-Gray, Maria; Schrüfer, Stefan; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Fleischmann, Bernd K.; Roell, Wilhelm; Engel, Felix (Advanced Materials, 2024)
Myocardial infarction (MI) causes cell death, disrupts electrical activity, triggers arrhythmia, and results in heart failure, whereby 50–60% of MI-associated deaths manifest as sudden cardiac deaths (SCD). The most effective therapy for SCD prevention is implantable cardioverter defibrillators (ICDs). However, ICDs contribute to adverse remodeling and disease progression and do not prevent arrhythmia. This work develops an injectable collagen-PEDOT:PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) hydrogel that protects infarcted hearts against ventricular tachycardia (VT) and can be combined with human induced pluripotent stem cell (hiPSC)-cardiomyocytes to promote partial cardiac remuscularization. PEDOT:PSS improves collagen gel formation, micromorphology, and conductivity. hiPSC-cardiomyocytes in collagen-PEDOT:PSS hydrogels exhibit near-adult sarcomeric length, improved contractility, enhanced calcium handling, and conduction velocity. RNA-sequencing data indicate enhanced maturation and improved cell-matrix interactions. Injecting collagen-PEDOT:PSS hydrogels in infarcted mouse hearts decreases VT to the levels of healthy hearts. Collectively, collagen-PEDOT:PSS hydrogels offer a versatile platform for treating cardiac injuries.
CRIS-Team Scopus Importer:2024-05-10
Keywords: arrhythmia; cardiac tissue engineering; collagen; electrically conductive; PEDOT:PSS

Electroconductive Biohybrid Hydrogel for Enhanced Maturation and Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Vogt, Lena; Greber, Boris; Diecke, Sebastian; Boccaccini, Aldo R.; Scheibel, Thomas; Engel, Felix (Advanced Functional Materials, 2018)
Keywords: electroconductive hydrogels; maturation; tissue engineering; heart; hiPSC

Enhancement of engineered cardiac tissues by promotion of hiPSC-cardiomyocyte proliferation - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Enhancing biofabrication: Shrink-resistant collagen-hyaluronan composite hydrogel for tissue engineering and 3D bioprinting applications - Roshanbinfar, Kaveh; Evans, Austin Donnelly; Samanta, Sumanta; Kolesnik-Gray, Maria; Fiedler, Maren; Krstic, Vojislav; Engel, Felix; Oommen, Oommen P. (Biomaterials, 2025)
Biofabrication represents a promising technique for creating tissues for regeneration or as models for drug testing. Collagen-based hydrogels are widely used as suitable matrix owing to their biocompatibility and tunable mechanical properties. However, one major challenge is that the encapsulated cells interact with the collagen matrix causing construct shrinkage. Here, we present a hydrogel with high shape fidelity, mimicking the major components of the extracellular matrix. We engineered a composite hydrogel comprising gallic acid (GA)-functionalized hyaluronic acid (HA), collagen I, and HA-coated multiwall carbon nanotubes (MWCNT). This hydrogel supports cell encapsulation, exhibits shear-thinning properties enhancing injectability and printability, and importantly significantly mitigates shrinkage when loaded with human fibroblasts compared to collagen I hydrogels (∼20 % vs. > 90 %). 3D-bioprinted rings utilizing human fibroblast-loaded inks maintain their shape over 7 days in culture. Furthermore, inclusion of HAGA into collagen I hydrogels increases mechanical stiffness, radical scavenging capability, and tissue adhesiveness. Notably, the here developed hydrogel is also suitable for human induced pluripotent stem cell-derived cardiomyocytes and allows printing of functional heart ventricles responsive to pharmacological treatment. Cardiomyocytes behave similar in the newly developed hydrogels compared to collagen I, based on survival, sarcomere appearance, and calcium handling. Collectively, we developed a novel material to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity.
CRIS-Team Scopus Importer:2025-02-21
Keywords: 3D bioprinting; Cardiac; Hydrogel; Shrink-resistant; Shrinkage; Tissue engineering

Enhancing Form Stability: Shrink-Resistant Hydrogels Made of Interpenetrating Networks of Recombinant Spider Silk and Collagen-I - Ng, Xuen J.; Esser, Tilman; Trossmann, Vanessa T.; Rudisch, Christoph; Fiedler, Maren; Roshanbinfar, Kaveh; Lamberger, Zan; Stahlhut, Philipp; Lang, Gregor; Scheibel, Thomas; Engel, Felix (Advanced Healthcare Materials, 2025)
Tissue engineering enables the production of tissues and organ-like structures as models for drug testing and mechanistical studies or functional replacements for injured tissues. Available cytocompatible materials are limited in number, suffer from insufficient mechanical properties, and cells interacting with them often cause construct shrinkage. As shape is important for function, identifying cytocompatible, shrink-resistant materials are a major aim. Here, it is shown that hydrogels made of interpenetrating networks of collagen-I and recombinant spider silk protein eADF4(C16)-RGD nanofibrils exhibit synergistic and tunable mechanical properties. Composite hydrogels allow cell adhesion and spreading and are resistant to shrinkage mediated by fibroblasts, C2C12 myoblasts, and human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. Myoblasts differentiate and fuse into myotubes, and hiPSC-cardiomyocytes can be cultured long-term, show spontaneous contractions, and remain drug responsive. Collectively, a novel composite material is developed to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity suitable for tissue engineering.
CRIS-Team Scopus Importer:2025-04-11
Keywords: biopolymer; cardiac tissue engineering; compaction; heart; shrinkage

Epigenomic and transcriptomic approaches in the post-genomic era: path to novel targets for diagnosis and therapy of the ischaemic heart? Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart - Perrino, Cinzia; Barabasi, Albert-Laszlo; Condorelli, Gianluigi; Davidson, Sean Michael; De Windt, Leon; Dimmeler, Stefanie; Engel, Felix; Hausenloy, Derek John; Hill, Joseph Addison; Van Laake, Linda Wilhelmina; Lecour, Sandrine; Leor, Jonathan; et al. (Cardiovascular Research, 2017)
Despite advances in myocardial reperfusion therapies, acute myocardial ischaemia/reperfusion injury and consequent ischaemic heart failure represent the number one cause of morbidity and mortality in industrialized societies. Although different therapeutic interventions have been shown beneficial in preclinical settings, an effective cardioprotective or regenerative therapy has yet to be successfully introduced in the clinical arena. Given the complex pathophysiology of the ischaemic heart, large scale, unbiased, global approaches capable of identifying multiple branches of the signalling networks activated in the ischaemic/reperfused heart might be more successful in the search for novel diagnostic or therapeutic targets. High-throughput techniques allow high-resolution, genome-wide investigation of genetic variants, epigenetic modifications, and associated gene expression profiles. Platforms such as proteomics and metabolomics (not described here in detail) also offer simultaneous readouts of hundreds of proteins and metabolites. Isolated omics analyses usually provide Big Data requiring large data storage, advanced computational resources and complex bioinformatics tools. The possibility of integrating different omics approaches gives new hope to better understand the molecular circuitry activated by myocardial ischaemia, putting it in the context of the human 'diseasome'. Since modifications of cardiac gene expression have been consistently linked to pathophysiology of the ischaemic heart, the integration of epigenomic and transcriptomic data seems a promising approach to identify crucial disease networks. Thus, the scope of this Position Paper will be to highlight potentials and limitations of these approaches, and to provide recommendations to optimize the search for novel diagnostic or therapeutic targets for acute ischaemia/reperfusion injury and ischaemic heart failure in the post-genomic era.
EVALuna2:25534

ESC Working Group Cellular Biology of the Heart: Position Paper: improving the preclinical assessment of novel cardioprotective therapies - Lecour, Sandrine; Botker, Hans E.; Condorelli, Gianluigi; Davidson, Sean M.; Garcia-Dorado, David; Engel, Felix; Ferdinandy, Peter; Heusch, Gerd; Madonna, Rosalinda; Ovize, Michel; Ruiz-Meana, Marisol; Schulz, Rainer; et al. (Cardiovascular Research, 2014)
Ischaemic heart disease (IHD) remains the leading cause of death and disability worldwide. As a result, novel therapies are still needed to protect the heart from the detrimental effects of acute ischaemia-reperfusion injury, in order to improve clinical outcomes in IHD patients. In this regard, although a large number of novel cardioprotective therapies discovered in the research laboratory have been investigated in the clinical setting, only a few of these have been demonstrated to improve clinical outcomes. One potential reason for this lack of success may have been the failure to thoroughly assess the cardioprotective efficacy of these novel therapies in suitably designed preclinical experimental animal models. Therefore, the aim of this Position Paper by the European Society of Cardiology Working Group Cellular Biology of the Heart is to provide recommendations for improving the preclinical assessment of novel cardioprotective therapies discovered in the research laboratory, with the aim of increasing the likelihood of success in translating these new treatments into improved clinical outcomes.
EVALuna2:25478

ESC Working Group on Cellular Biology of the Heart: Tissue Engineering and Cell-Based Therapies for Cardiac Repair in Ischemic Heart Disease and Heart Failure - Madonna, Rosalinda; Van Laake, Linda W.; Botker, Hans Erik; Davidson, Sean M.; De Caterina, Raffaele; Engel, Felix; Eschenhagen, Thomas; Fernandez-Aviles, Francesco; Hausenloy, Derek J.; Hulot, Jean Sebastien; Lecour, Sandrine; Leor, Jonathan; et al. (Cardiovascular Research, 2019)
Morbidity and mortality from ischemic heart disease (IHD) and heart failure (HF) remain significant in Europe and are increasing worldwide. Patients with IHD or HF might benefit from novel therapeutic strategies, such as cell-based therapies. We recently discussed the therapeutic potential of cell-based therapies and provided recommendations on how to improve the therapeutic translation of these novel strategies for effective cardiac regeneration and repair. Despite major advances in optimizing these strategies with respect to cell source and delivery method, the clinical outcome of cell-based therapy remains unsatisfactory. Major obstacles are the low engraftment and survival rate of transplanted cells in the harmful microenvironment of the host tissue, and the paucity or even lack of endogenous cells with repair capacity. Therefore, new ways of delivering cells and their derivatives are required in order to empower cell-based cardiac repair and regeneration in patients with IHD or HF. Strategies using tissue engineering (TE) combine cells with matrix materials to enhance cell retention or cell delivery in the transplanted area, and have recently received much attention for this purpose. Here, we summarize knowledge on novel approaches emerging from the TE scenario. In particular, we will discuss how combinations of cell/bio-materials (e.g., hydrogels, cell sheets, prefabricated matrices, microspheres, and injectable matrices) combinations might enhance cell retention or cell delivery in the transplantation areas and thereby increase the success rate of cell therapies for IHD and HF. We will not focus on the use of classical engineering approaches, employing fully synthetic materials, because of their unsatisfactory material properties which render them not clinically applicable. The overall aim of this Position Paper from the ESC Working Group Cellular Biology of the Heart is to provide recommendations on how to proceed in research with these novel tissue engineering strategies combined with cell-based therapies to boost cardiac repair in the clinical settings of IHD and HF.
EVALuna2:35428

Extracellular vesicles in diagnostics and therapy of the ischaemic heart: Position Paper from the Working Group on Cellular Biology of the Heart of the European Society of Cardiology - Sluijter, Joost Petrus Gerardus; Davidson, Sean Michael; Boulanger, Chantal M.; Buzas, Edit Iren; De Kleijn, Dominique Paschalis Victor; Engel, Felix; Giricz, Zoltan; Hausenloy, Derek J.; Kishore, Raj; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; et al. (Cardiovascular Research, 2018)
Extracellular vesicles (EVs)-particularly exosomes and microvesicles (MVs)-are attracting considerable interest in the cardiovascular field as the wide range of their functions is recognized. These capabilities include transporting regulatory molecules including different RNA species, lipids, and proteins through the extracellular space including blood and delivering these cargos to recipient cells to modify cellular activity. EVs powerfully stimulate angiogenesis, and can protect the heart against myocardial infarction. They also appear to mediate some of the paracrine effects of cells, and have therefore been proposed as a potential alternative to cell-based regenerative therapies. Moreover, EVs of different sources may be useful biomarkers of cardiovascular disease identities. However, the methods used for the detection and isolation of EVs have several limitations and vary widely between studies, leading to uncertainties regarding the exact population of EVs studied and how to interpret the data. The number of publications in the exosome and MV field has been increasing exponentially in recent years and, therefore, in this ESC Working Group Position Paper, the overall objective is to provide a set of recommendations for the analysis and translational application of EVs focussing on the diagnosis and therapy of the ischaemic heart. This should help to ensure that the data from emerging studies are robust and repeatable, and optimize the pathway towards the diagnostic and therapeutic use of EVs in clinical studies for patient benefit.
EVALuna2:25557

FGF1-mediated cardiomyocyte cell cycle reentry depends on the interaction of FGFR-1 and Fn14 - Novoyatleva, Tatyana; Sajjad, Amna; Pogoryelov, Denys; Patra, Chinmoy; Schermuly, Ralph T.; Engel, Felix (The FASEB Journal, 2014)
Fibroblast growth factors (FGFs) signal through FGF receptors (FGFRs) mediating a broad range of cellular functions during embryonic development, as well as disease and regeneration during adulthood. Thus, it is important to understand the underlying molecular mechanisms that modulate this system. Here, we show that FGFR-1 can interact with the TNF receptor superfamily member fibroblast growth factor-inducible molecule 14 (Fn14) resulting in cardiomyocyte cell cycle reentry. FGF1-induced cell cycle reentry in neonatal cardiomyocytes could be blocked by Fn14 inhibition, while TWEAK-induced cell cycle activation was inhibited by blocking FGFR-1 signaling. In addition, costimulation experiments revealed a synergistic effect of FGF1 and TWEAK in regard to cardiomyocyte cell cycle induction via PI3K/Akt signaling. Overexpression of Fn14 with either FGFR-1 long [FGFR-1(L)] or FGFR-1 short [FGFR-1(S)] isoforms resulted after FGF1/TWEAK stimulation in cell cycle reentry of >40% adult cardiomyocytes. Finally, coimmunoprecipitation and proximity ligation assays indicated that endogenous FGFR-1 and Fn14 interact with each other in cardiomyocytes. This interaction was strongly enhanced in the presence of their corresponding ligands, FGF1 and TWEAK. Taken together, our data suggest that FGFR-1/Fn14 interaction may represent a novel endogenous mechanism to modulate the action of these receptors and their ligands and to control cardiomyocyte cell cycle reentry.
EVALuna2:25462

From basic mechanisms to clinical applications in heart protection, new players in cardiovascular diseases and cardiac theranostics: meeting report from the third international symposium on "New frontiers in cardiovascular research" - Cabrera-Fuentes, Hector A.; Aragones, Julian; Bernhagen, Juergen; Boening, Andreas; Boisvert, William A.; Botker, Hans E.; Bulluck, Heerajnarain; Cook, Stuart; Di Lisa, Fabio; Engel, Felix; Engelmann, Bernd; Ferrazzi, Fulvia; et al. (Basic Research in Cardiology, 2016)
In this meeting report, particularly addressing the topic of protection of the cardiovascular system from ischemia/reperfusion injury, highlights are presented that relate to conditioning strategies of the heart with respect to molecular mechanisms and outcome in patients' cohorts, the influence of co-morbidities and medications, as well as the contribution of innate immune reactions in cardioprotection. Moreover, developmental or systems biology approaches bear great potential in systematically uncovering unexpected components involved in ischemia-reperfusion injury or heart regeneration. Based on the characterization of particular platelet integrins, mitochondrial redox-linked proteins, or lipid-diol compounds in cardiovascular diseases, their targeting by newly developed theranostics and technologies opens new avenues for diagnosis and therapy of myocardial infarction to improve the patients' outcome.
EVALuna2:9341

Functional genomics meta-analysis to identify gene set enrichment networks in cardiac hypertrophy - Angeloni, Miriam; Thievessen, Ingo; Engel, Felix; Magni, Paolo; Ferrazzi, Fulvia (Biological Chemistry, 2021)
In order to take advantage of the continuously increasing number of transcriptome studies, it is important to develop strategies that integrate multiple expression datasets addressing the same biological question to allow a robust analysis. Here, we propose a meta-analysis framework that integrates enriched pathways identified through the Gene Set Enrichment Analysis (GSEA) approach and calculates for each meta-pathway an empirical p-value. Validation of our approach on benchmark datasets showed comparable or even better performance than existing methods and an increase in robustness with increasing number of integrated datasets. We then applied the meta-analysis framework to 15 functional genomics datasets of physiological and pathological cardiac hypertrophy. Within these datasets we grouped expression sets measured at time points that represent the same hallmarks of heart tissue remodeling ('aggregated time points') and performed meta-analysis on the expression sets assigned to each aggregated time point. To facilitate biological interpretation, results were visualized as gene set enrichment networks. Here, our meta-analysis framework identified well-known biological mechanisms associated with pathological cardiac hypertrophy (e.g., cardiomyocyte apoptosis, cardiac contractile dysfunction, and alteration in energy metabolism). In addition, results highlighted novel, potentially cardioprotective mechanisms in physiological cardiac hypertrophy involving the down-regulation of immune cell response, which are worth further investigation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cardiac hypertrophy; pathological hypertrophy; pathway network; physiological hypertrophy; transcriptome meta-analysis

GAS2L3: Coordinator of cardiomyocyte cytokinesis? - Gruendl, Marco; Engel, Felix; Gaubatz, Stefan (Cell Cycle, 2017)
EVALuna2:25554

Gelatin methacryloyl is a slow degrading material allowing vascularization and long-term use in vivo - Heltmann-Meyer, Stefanie; Steiner, Dominik; Mueller, Claudia; Schneidereit, Dominik; Friedrich, Oliver; Salehi, Sahar; Engel, Felix; Arkudas, Andreas; Horch, Raymund E. (Biomedical Materials, 2021)
In situ tissue engineering is an emerging field aiming at the generation of ready-to-use three-dimensional tissues. One solution to supply a proper vascularization of larger tissues to provide oxygen and nutrients is the arteriovenous loop (AVL) model. However, for this model, suitable scaffold materials are needed that are biocompatible/non-immunogenic, slowly degradable, and allow vascularization. Here, we investigate the suitability of the known gelatin methacryloyl (GelMA)-based hydrogel for in-situ tissue engineering utilizing the AVL model. Rat AVLs are embedded by two layers of GelMA hydrogel in an inert PTFE chamber and implanted in the groin. Constructs were explanted after 2 or 4 weeks and analyzed. For this purpose, gross morphological, histological, and multiphoton microscopic analysis were performed. Immune response was analyzed based on anti-CD68 and anti-CD163 staining of immune cells. The occurrence of matrix degradation was assayed by anti-MMP3 staining. Vascularization was analyzed by anti-alpha-smooth muscle actin staining, multiphoton microscopy, as well as expression analysis of 53 angiogenesis-related proteins utilizing a proteome profiler angiogenesis array kit. Here we show that GelMA hydrogels are stable for at least 4 weeks in the rat AVL model. Furthermore, our data indicate that GelMA hydrogels are biocompatible. Finally, we provide evidence that GelMA hydrogels in the AVL model allow connective tissue formation, as well as vascularization, introducing multiphoton microscopy as a new methodology to visualize neovessel formation originating from the AVL. GelMA is a suitable material for in situ and in vivo TE in the AVL model.
CRIS-Team WoS Importer:2021-09-17

Gene network analysis: from heart development to cardiac therapy - Ferrazzi, Fulvia; Bellazzi, Riccardo; Engel, Felix (Thrombosis and Haemostasis, 2015)
Networks offer a flexible framework to represent and analyse the complex interactions between components of cellular systems. In particular gene networks inferred from expression data can support the identification of novel hypotheses on regulatory processes. In this review we focus on the use of gene network analysis in the study of heart development. Understanding heart development will promote the elucidation of the aetiology of congenital heart disease and thus possibly improve diagnostics. Moreover, it will help to establish cardiac therapies. For example, understanding cardiac differentiation during development will help to guide stem cell differentiation required for cardiac tissue engineering or to enhance endogenous repair mechanisms. We introduce different methodological frameworks to infer networks from expression data such as Boolean and Bayesian networks. Then we present currently available temporal expression data in heart development and discuss the use of network-based approaches in published studies. Collectively, our literature-based analysis indicates that gene network analysis constitutes a promising opportunity to infer therapy-relevant regulatory processes in heart development. However, the use of network-based approaches has so far been limited by the small amount of samples in available datasets. Thus, we propose to acquire high-resolution temporal expression data to improve the mathematical descriptions of regulatory processes obtained with gene network inference methodologies. Especially probabilistic methods that accommodate the intrinsic variability of biological systems have the potential to contribute to a deeper understanding of heart development.
EVALuna2:9255

Gpr126 (Adgrg6) is expressed in cell types known to be exposed to mechanical stimuli - Musa, Gentian; Cazorla-Vázquez, Salvador; van Amerongen, Machteld J.; Stemmler, Marc; Eckstein, Markus; Hartmann, Arndt; Braun, Thomas; Brabletz, Thomas; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
GPR126 (ADGRG6) is an adhesion G protein–coupled receptor that plays an important role in a variety of tissues/organs, such as heart, sciatic nerve, cartilage, and ear. Moreover, GPR126 (ADGRG6) mutations are associated with human diseases, like adolescent idiopathic scoliosis, lung disease, bladder cancer, and intellectual disability. Despite its clinical importance, it remains elusive how GPR126 is activated and mediates signal transduction and what cellular processes depend on GPR126 signaling. Here, we generated a lacZ reporter mouse line to determine endogenous Gpr126 (Adgrg6) expression in a cell type-specific manner during embryonic development, at postnatal day 5 and in adult animals. Our results confirm Gpr126 expression data previously obtained utilizing antibodies and in situ hybridization in embryonic heart and sciatic nerve. In addition, we provide data with cellular resolution for previously described RT-PCR–based data, including lung and bladder. Moreover, new Gpr126-expressing tissues and cell types were identified, such as ureter and acinar secretory cells. Collectively, our data demonstrate that the newly generated lacZ reporter mouse is a suitable model to study Gpr126 expression during development and adulthood, provide detailed insight into Gpr126 expression at the cellular level, and reveal that all identified Gpr126-expressing cells are known to be exposed to mechanical stimuli.
CRIS-Team Scopus Importer:2019-06-28
Keywords: ADGRG6; chondrocytes; endothelium; epithelium

Gpr126 domains control different cellular mechanisms of ventricular chamber development - Srivastava, Swati; Gunanwan, F.; Guenther, S.; Ferrazzi, Fulvia; Gentile, A.; Monk, K. M.; Stainier, D. Y. R.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
Trabeculation is a crucial process during ventricular chamber development which describes the protrusion of cardiomyocytes into the lumen of the ventricular chamber to form complex muscular structures called trabeculae. Defects in this process results in various human diseases such as left ventricular non compaction cardiomyopathies and other congenital heart defects. Several cellular mechanisms have been identified underlying trabeculation including tension heterogeneity induced cardiomyocyte selection, depolarization and delamination. However, the molecular mechanisms governing trabeculation are still poorly understood.<br
CRIS-Team WoS Importer:2021-12-10

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

Heart Development, Angiogenesis, and Blood-Brain Barrier Function Is Modulated by Adhesion GPCRs - Musa, Gentian; Engel, Felix; Niaudet, Colin (Handbook of experimental pharmacology, 2016)
The cardiovascular system in adult organisms forms a network of interconnected endothelial cells, supported by mural cells and displaying a high degree of hierarchy: arteries emerging from the heart ramify into arterioles and then capillaries, which return to the venous systems through venules and veins. The cardiovascular system allows blood circulation, which in turn is essential for hemostasis through gas diffusion, nutrient distribution, and cell trafficking. In this chapter, we have summarized the current knowledge on how adhesion GPCRs (aGPCRs) impact heart development, followed by their role in modulating vascular angiogenesis.
EVALuna2:25530

Human cytomegaloviral multifunctional protein kinase pUL97 impairs zebrafish embryonic development and increases mortality - Cazorla-Vázquez, Salvador; Steingruber, Mirjam; Marschall, Manfred; Engel, Felix (Scientific Reports, 2019)
Cytomegalovirus is a worldwide-distributed human pathogen, which is the leading cause of congenital virus infection, affecting 0.5 to 2% of live births. To date, it is largely unclear which molecular mechanisms underlie the symptomatic outcomes. This is mainly due to species specificity and limited homology among cytomegalovirus genomes. As it is not possible to infect model organisms with human cytomegalovirus, the aim of this study was to develop a heterologous system allowing in the future the elucidation of the pathological role of individual viral proteins. As a model organism the zebrafish has been chosen due to its ease of manipulation and characterization as well as its large offspring. As cytomegalovirus model protein, pUL97 was characterized because it is multiply involved in virus-host interaction. Here, we show in zebrafish embryos, that (i) pUL97 can be expressed in zebrafish, (ii) increasing pUL97 expression levels quantitatively correlate with both minor and major pathological defects, (iii) pUL97 expression impairs cell cycle progression and induces cell death, (iv) active pUL97, but not an inactive mutant, induces excess mortality, and (v) co-administration of a pUL97 inhibitor reduces embryonic pathology. Collectively, these data indicate the suitability of zebrafish to elucidate the pathological role of human cytomegaloviral proteins.
CRIS-Team Scopus Importer:2019-05-24

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

Improvement of the Layer Adhesion of Composite Cardiac Patches - Ruther, Florian; Zimmermann, Andrea; Engel, Felix; Boccaccini, Aldo R. (Advanced Engineering Materials, 2019)
The major purpose of cardiac patches is to deliver healthy cells to infarcted tissues. Such cardiac patches must fulfill specific mechanical as well as chemical requirements. Herein, bi-component cardiac patches are investigated with regard to their layer adhesion. Combinations of salt-leached porous poly (glycerol sebacate) (PGS) films with a layer of electrospun-gelatin fibers are produced. Gelatin fibers are fabricated by solution electrospinning using 20 wt% gelatin in 98 v% formic acid. Fibers are attached to PGS films either via direct electrospinning on top of the film or via combining as spun fiber mats with PGS using gelatin as glue. Scanning electron microscopy (SEM) images show that fiber mats adapt to the rough surface of the porous PGS film. In contrast, fibers spun directly onto films show poor adhesion and only a few fibers are attached to the PGS substrate. Fourier transform infrared (FTIR) analysis, contact-angle measurements, and pull-off adhesion tests of the bi-component patches confirm these results. Modified pull-off adhesion tests of the two layers show that combining as spun gelatin fiber mats with porous PGS substrates by gluing leads to excellent material adhesion before and after incubation for up to 14 days.
CRIS-Team Scopus Importer:2019-11-19
Keywords: bi-layer adhesions; cardiac patches; electrospinning; gelatin; porous poly (glycerol sebacate)

Improving translational research in sex-specific effects of comorbidities and risk factors in ischaemic heart disease and cardioprotection: position paper and recommendations of the ESC Working Group on Cellular Biology of the Heart - Perrino, Cinzia; Ferdinandy, Péter; Bøtker, Hans E.; Brundel, Bianca J.J.M.; Collins, Peter; Davidson, Sean M.; den Ruijter, Hester M.; Engel, Felix; Gerdts, Eva; Girao, Henrique; Gyöngyösi, Mariann; Hausenloy, Derek J.; et al. (Cardiovascular Research, 2021)
Ischaemic heart disease (IHD) is a complex disorder and a leading cause of death and morbidity in both men and women. Sex, however, affects several aspects of IHD, including pathophysiology, incidence, clinical presentation, diagnosis as well as treatment and outcome. Several diseases or risk factors frequently associated with IHD can modify cellular signalling cascades, thus affecting ischaemia/reperfusion injury as well as responses to cardioprotective interventions. Importantly, the prevalence and impact of risk factors and several comorbidities differ between males and females, and their effects on IHD development and prognosis might differ according to sex. The cellular and molecular mechanisms underlying these differences are still poorly understood, and their identification might have important translational implications in the prediction or prevention of risk of IHD in men and women. Despite this, most experimental studies on IHD are still undertaken in animal models in the absence of risk factors and comorbidities, and assessment of potential sex-specific differences are largely missing. This ESC WG Position Paper will discuss: (i) the importance of sex as a biological variable in cardiovascular research, (ii) major biological mechanisms underlying sex-related differences relevant to IHD risk factors and comorbidities, (iii) prospects and pitfalls of preclinical models to investigate these associations, and finally (iv) will provide recommendations to guide future research. Although gender differences also affect IHD risk in the clinical setting, they will not be discussed in detail here.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cardioprotection Sex differences Ischaemic heart disease Ischaemia and reperfusion Translational research Comorbidities

Incorporation of montmorillonite into microfluidics-generated chitosan microfibers enhances neuron-like PC12 cells for application in neural tissue engineering - Katoli, Zahra; Navaei-Nigjeh, Mona; Mirzababaei, Soheyl; Sabahi, Hossein; Baeeri, Maryam; Akrami, Mohammad; Roshanbinfar, Kaveh; Engel, Felix; Abdollahi, Mohammad (Carbohydrate Polymers, 2024)
The complexity in structure and function of the nervous system, as well as its slow rate of regeneration, makes it more difficult to treat it compared to other tissues. Neural tissue engineering aims to create an appropriate environment for nerve cell proliferation and differentiation. Fibrous scaffolds with suitable morphology and topography and better mimicry of the extracellular matrix have been promising for the alignment and migration of neural cells. On this premise, to improve the properties of the scaffold, we combined montmorillonite (MMT) with chitosan (CS) polymer and created microfibers with variable diameters and varied concentrations of MMT using microfluidic technology and tested its suitability for the rat pheochromocytoma cell line (PC12). According to the findings, CS/MMT 0.1 % compared to CS/MMT 0 % microfibers showed a 201 MPa increase in Young's modulus, a 68 mS/m increase in conductivity, and a 1.4-fold increase in output voltage. Analysis of cell mitochondrial activity verified the non-toxicity, resulting in good cell morphology with orientation along the microfiber. Overall, the results of this project showed that with a low concentration of MMT, the properties of microfibers can be significantly improved and a suitable scaffold can be designed for neural tissue engineering.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Chitosan; Microfiber; Microfluidic technology; Montmorillonite; Neural tissue engineering

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

International Union of Basic and Clinical Pharmacology. XCIV. Adhesion G protein-coupled receptors - Hamann, Joerg; Aust, Gabriela; Arac, Demet; Engel, Felix; Formstone, Caroline; Fredriksson, Robert; Hall, Randy A.; Harty, Breanne L.; Kirchhoff, Christiane; Knapp, Barbara; Krishnan, Arunkumar; Liebscher, Ines; et al. (Pharmacological Reviews, 2015)
The Adhesion family forms a large branch of the pharmacologically important superfamily of G protein-coupled receptors (GPCRs). As Adhesion GPCRs increasingly receive attention from a wide spectrum of biomedical fields, the Adhesion GPCR Consortium, together with the International Union of Basic and Clinical Pharmacology Committee on Receptor Nomenclature and Drug Classification, proposes a unified nomenclature for Adhesion GPCRs. The new names have ADGR as common dominator followed by a letter and a number to denote each subfamily and subtype, respectively. The new names, with old and alternative names within parentheses, are: ADGRA1 (GPR123), ADGRA2 (GPR124), ADGRA3 (GPR125), ADGRB1 (BAI1), ADGRB2 (BAI2), ADGRB3 (BAI3), ADGRC1 (CELSR1), ADGRC2 (CELSR2), ADGRC3 (CELSR3), ADGRD1 (GPR133), ADGRD2 (GPR144), ADGRE1 (EMR1, F4/80), ADGRE2 (EMR2), ADGRE3 (EMR3), ADGRE4 (EMR4), ADGRE5 (CD97), ADGRF1 (GPR110), ADGRF2 (GPR111), ADGRF3 (GPR113), ADGRF4 (GPR115), ADGRF5 (GPR116, Ig-Hepta), ADGRG1 (GPR56), ADGRG2 (GPR64, HE6), ADGRG3 (GPR97), ADGRG4 (GPR112), ADGRG5 (GPR114), ADGRG6 (GPR126), ADGRG7 (GPR128), ADGRL1 (latrophilin-1, CIRL-1, CL1), ADGRL2 (latrophilin-2, CIRL-2, CL2), ADGRL3 (latrophilin-3, CIRL-3, CL3), ADGRL4 (ELTD1, ETL), and ADGRV1 (VLGR1, GPR98). This review covers all major biologic aspects of Adhesion GPCRs, including evolutionary origins, interaction partners, signaling, expression, physiologic functions, and therapeutic potential.
EVALuna2:25498

IQGAP3, a YAP target, is required for proper cell-cycle progression and genome stability - Leone, Marina; Cazorla-Vazquez, Salvador; Ferrazzi, Fulvia; Wiederstein, Janica L.; Grundl, Marco; Weinstock, Grit; Vergarajauregui, Silvia; Eckstein, Markus; Kruger, Marcus; Gaubatz, Stefan; Engel, Felix (Molecular Cancer Research, 2021)
Controlling cell proliferation is critical for organism development, tissue homeostasis, disease, and regeneration. IQGAP3 has been shown to be required for proper cell proliferation and migration, and is associated to a number of cancers. Moreover, its expression is inversely correlated with the overall survival rate in the majority of cancers. Here, we show that IQGAP3 expression is elevated in cervical cancer and that in these cancers IQGAP3 high expression is correlated with an increased lethality. Furthermore, we demonstrate that IQGAP3 is a target of YAP, a regulator of cell cycle gene expression. IQGAP3 knockdown resulted in an increased percentage of HeLa cells in S phase, delayed progression through mitosis, and caused multipolar spindle formation and consequentially aneuploidy. Protein–protein interaction studies revealed that IQGAP3 interacts with MMS19, which is known in Drosophila to permit, by competitive binding to Xpd, Cdk7 to be fully active as a Cdk-activating kinase (CAK). Notably, IQGAP3 knockdown caused decreased MMS19 protein levels and XPD knockdown partially rescued the reduced proliferation rate upon IQGAP3 knockdown. This suggests that IQGAP3 modulates the cell cycle via the MMS19/XPD/CAK axis. Thus, in addition to governing proliferation and migration, IQGAP3 is a critical regulator of mitotic progression and genome stability. Implications: Our data indicate that, while IQGAP3 inhibition might be initially effective in decreasing cancer cell proliferation, this approach harbors the risk to promote aneuploidy and, therefore, the formation of more aggressive cancers.
CRIS-Team Scopus Importer:2021-11-05

Isolation, Culture, and Live-Cell Imaging of Primary Rat Cardiomyocytes - Leone, Marina; Engel, Felix (Methods in Molecular Biology, 2021)
The heart is a complex organ consisting of a variety of different cardiomyocytes (ventricular vs. atrial, left vs. right ventricular, working vs. nodal) as well as other cell types, including endothelial cells and vascular smooth muscle cells. Pericytes, neurons, and immune cells are less abundant, yet still important. Whereas cardiomyocytes account for around 75% of the heart volume, 50-70% of the cells in the heart are non-myocytes. This complexity of the heart underlines the difficulties in interpreting data obtained in vivo. In the field of cardiac regeneration, it remains unclear whether it is possible to induce a significant number of cardiomyocytes to proliferate and whether the often-observed improvement in cardiac function after experimental therapies is due to the induction of cardiomyocyte proliferation. Therefore, the reductionist approach inherent to cultures of isolated cells continues to be of great importance, even though it is important to study heart disease in vivo due to interactions of the different cell types. Cultured cardiomyocytes allow for easy manipulation of cell behavior (e.g., cell division) and its analysis (e.g., live-cell imaging). In addition, isolated cells in culture are a valuable tool for pharmacological and toxicological studies. This chapter offers a practical guide to isolate and culture primary neonatal and adult rat cardiomyocytes and a detailed protocol for live-cell imaging of embryonic and neonatal cardiomyocytes.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Adult; Cardiomyocytes; Langendorff-perfusion; Live-cell imaging; MACS; Neonatal; Rat; SADO Mix

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

Large-scale microRNA functional high-throughput screening identifies miR-515-3p and miR-519e-3p as inducers of human cardiomyocyte proliferation - Renikunta, Harsha V.; Lazarow, Katina; Gong, Yiqi; Shukla, Praphulla Chandra; Nageswaran, Vanasa; Giral, Hector; Kratzer, Adelheid; Opitz, Lennart; Engel, Felix; Haghikia, Arash; Costantino, Sarah; Paneni, Francesco; et al. (iScience, 2023)
Ischemic cardiomyopathy, driven by loss of cardiomyocytes and inadequate proliferative response, persists to be a major global health problem. Using a functional high-throughput screening, we assessed differential proliferative potential of 2019 miRNAs after transient hypoxia by transfecting both miR-inhibitor and miR-mimic libraries in human iPSC-CM. Whereas miR-inhibitors failed to enhance EdU uptake, overexpression of 28 miRNAs substantially induced proliferative activity in hiPSC-CM, with an overrepresentation of miRNAs belonging to the primate-specific C19MC-cluster. Two of these miRNAs, miR-515-3p and miR-519e-3p, increased markers of early and late mitosis, indicative of cell division, and substantially alter signaling pathways relevant for cardiomyocyte proliferation in hiPSC-CM.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Cardiovascular medicine; Genetics; Molecular biology

Live cell screening identifies glycosides as enhancers of cardiomyocyte cell cycle activity - Magadum, Ajit; Renikunta, Harsha V.; Singh, Neha; Estaras, Conchi; Kishore, Raj; Engel, Felix (Frontiers in Cardiovascular Medicine, 2022)
Promoting cardiomyocyte proliferation is a promising strategy to regenerate the heart. Yet, so far, it is poorly understood how cardiomyocyte proliferation is regulated, and no factor identified to promote mammalian cardiomyocyte proliferation has been translated into medical practice. Therefore, finding a novel factor will be vital. Here, we established a live cell screening based on mouse embryonic stem cell-derived cardiomyocytes expressing a non-functional human geminin deletion mutant fused to Azami Green (CM7/1-hgem-derived cardiomyocytes). We screened for a subset of compounds of the small molecule library Spectrum Collection and identified 19 potential inducers of stem cell-derived cardiomyocyte proliferation. Furthermore, the pro-proliferative potential of identified candidate compounds was validated in neonatal and adult rat cardiomyocytes as well as human induced pluripotent stem cell-derived cardiomyocytes. 18 of these compounds promoted mitosis and cytokinesis in neonatal rat cardiomyocytes. Among the top four candidates were two cardiac glycosides, peruvoside and convallatoxin, the flavonoid osajin, and the selective α-adrenoceptor antagonist and imidazoline I1 receptor ligand efaroxan hydrochloride. Inhibition of PTEN and GSK-3β enhanced cell cycle re-entry and progression upon stimulation with cardiac glycosides and osajin, while inhibition of IP3 receptors inhibited the cell cycle-promoting effect of cardiac glycosides. Collectively, we established a screening system and identified potential compounds to promote cardiomyocyte proliferation. Our data suggest that modulation of calcium handling and metabolism promotes cardiomyocyte proliferation, and cardiac glycosides might, besides increasing myocardial contraction force, contribute to cardiac repair by inducing cardiomyocyte proliferation.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Azami Green; calcium handling; cardiac glycosides; cardiomyocyte proliferation; cell cycle; live cell screening platform AG; small molecules; stem cell

Live cell screening platform identifies PPAR? as a regulator of cardiomyocyte proliferation and cardiac repair - Magadum, Ajit; Ding, Yishu; He, Lan; Kim, Teayoun; Vasudevarao, Mohankrishna Dalvoy; Long, Qinqiang; Yang, Kevin; Wickramasinghe, Nadeera; Renikunta, Harsha V.; Dubois, Nicole; Weidinger, Gilbert; Yang, Qinglin; et al. (Cell Research, 2017)
Zebrafish can efficiently regenerate their heart through cardiomyocyte proliferation. In contrast, mammalian cardiomyocytes stop proliferating shortly after birth, limiting the regenerative capacity of the postnatal mammalian heart. Therefore, if the endogenous potential of postnatal cardiomyocyte proliferation could be enhanced, it could offer a promising future therapy for heart failure patients. Here, we set out to systematically identify small molecules triggering postnatal cardiomyocyte proliferation. By screening chemical compound libraries utilizing a Fucci-based system for assessing cell cycle stages, we identified carbacyclin as an inducer of postnatal cardiomyocyte proliferation. In vitro, carbacyclin induced proliferation of neonatal and adult mononuclear rat cardiomyocytes via a peroxisome proliferator-activated receptor ? (PPAR?)/PDK1/p308Akt/GSK3?/?-catenin pathway. Inhibition of PPAR? reduced cardiomyocyte proliferation during zebrafish heart regeneration. Notably, inducible cardiomyocyte-specific overexpression of constitutively active PPAR? as well as treatment with PPAR? agonist after myocardial infarction in mice induced cell cycle progression in cardiomyocytes, reduced scarring, and improved cardiac function. Collectively, we established a cardiomyocyte proliferation screening system and present a new drugable target with promise for the treatment of cardiac pathologies caused by cardiomyocyte loss.
EVALuna2:25555
Keywords: cardiac repair; cardiomyocyte proliferation; screening; carbacyclin; PPAR delta; GSK3 beta; Tbx20

Lysine methyltransferase Smyd2 suppresses p53-dependent cardiomyocyte apoptosis - Sajjad, Amna; Novoyatleva, Tatyana; Vergarajauregui, Silvia; Troidl, Christian; Schermuly, Ralph T.; Tucker, Haley O.; Engel, Felix (Biochimica Et Biophysica Acta-Molecular Cell Research, 2014)
Apoptosis, or programmed cell death, is an essential physiological process for proper embryogenesis as well as for homeostasis during aging. In addition, apoptosis is one of the major mechanisms causing cell loss in pathophysiological conditions such as heart failure. Thus, inhibition of apoptosis is an important approach for preventive and therapeutic strategies. Here we show that the histone 3 lysine 4- and lysine 36-specific methyltransferase Smyd2 acts as an endogenous antagonistic player of p53-dependent cardiomyocyte apoptosis. Smyd2 protein levels were significantly decreased in cardiomyocytes upon cobalt chloride-induced apoptosis or myocardial infarction, while p53 expression was enhanced. siRNA-mediated knockdown of Smyd2 in cultured cardiomyocytes further enhanced cobalt chloride-induced cardiomyocyte apoptosis. In contrast, Smyd2 overexpression resulted in marked methylation of p53 and prevented its accumulation as well as apoptotic cell death in an Hsp90-independent manner. Moreover, overexpression, of Smyd2, but not Smyd2Y240F lacking a methyl transferase activity, significantly rescued CoCl2-induced apoptosis in H9c2 cardioblasts. Finally, Smyd2 cardiomyocyte-specific deletion in vivo promoted apoptotic cell death upon myocardial infarction, which correlated with enhanced expression of p53 and pro-apoptotic Bax. Collectively, our data indicate Smyd2 as a cardioprotective protein by methylating p53.
EVALuna2:25466

Melatonin as a cardioprotective therapy following ST-segment elevation myocardial infarction: is it really promising? Reply - Hausenloy, Derek J.; Garcia-Dorado, David; Botker, Hans Erik; Davidson, Sean M.; Downey, James; Engel, Felix; Jennings, Robert; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; Ovize, Michel; Perrino, Cinzia; et al. (Cardiovascular Research, 2017)
EVALuna2:25553

Microtubule Organization in Striated Muscle Cells - Becker, Robert; Leone, Marina; Engel, Felix (Cells, 2020)
Distinctly organized microtubule networks contribute to the function of differentiated cell types such as neurons, epithelial cells, skeletal myotubes, and cardiomyocytes. In striated (i.e. skeletal and cardiac) muscle cells, the nuclear envelope acts as the dominant microtubule-organizing center (MTOC) and the function of the centrosome-the canonical MTOC of mammalian cells-is attenuated, a common feature of differentiated cell types. We summarize the mechanisms known to underlie MTOC formation at the nuclear envelope, discuss the significance of the nuclear envelope MTOC for muscle function and cell cycle progression, and outline potential mechanisms of centrosome attenuation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cardiomyocytes; cell cycle; centrosome; microtubules; MTOC; non-centrosomal MTOC; skeletal muscle

miR-27a/b is a posttranscriptional regulator of Gpr126 (Adgrg6) - Musa, Gentian; Srivastava, Swati; Petzold, Jana; Cazorla-Vazquez, Salvador; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
Gpr126 (Adgrg6), a member of the adhesion G protein-coupled receptor family, has been associated with a variety of human diseases. Yet, despite its clinical importance, the mechanisms regulating Gpr126 expression are poorly understood. Here, we aimed at identifying upstream regulatory mechanisms of Gpr126 expression utilizing the heart as model organ in which Gpr126 regulates trabeculation. Here, we focused on possible regulation of Gpr126 regulation by microRNAs, which have emerged as key players in regulating development, have a critical role in disease progression, and might serve as putative therapeutic targets. In silico analyses identified one conserved binding site in the 3 ' UTR of Gpr126 for microRNA 27a and 27b (miR-27a/b). In addition, miR-27a/b and Gpr126 expression were differentially expressed during rat heart development. A regulatory role of miR-27a/b in controlling Gpr126 expression was substantiated by reduced Gpr126 mRNA levels upon ectopic expression of miR-27a/b in HEK293T cells and miR-27b in zebrafish embryos. Regulation of Gpr126 expression by direct binding of miR-27a/b to the 3 ' UTR of Gpr126 was verified by luciferase reporter assays in HEK293T cells. Finally, the modulation of gpr126 expression in zebrafish by injection of either miR-27b or miR-27b inhibitor in single cell-stage embryos resulted in hypo- or hypertrabeculation, respectively. Collectively, the data indicate that Gpr126 expression is regulated by miR-27a/b.
CRIS-Team WoS Importer:2019-10-22

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Nanofibrous Composite with Tailorable Electrical and Mechanical Properties for Cardiac Tissue Engineering - Roshanbinfar, Kaveh; Vogt, Lena; Ruther, Florian; Roether, Judith; Boccaccini, Aldo R.; Engel, Felix (Advanced Functional Materials, 2019)
Cardiac tissue engineering is a promising strategy to prevent functional deterioration or even to enhance cardiac function upon myocardial infarction. Here, electrospun fiber mats containing different combinations of electrically conductive polyaniline, collagen, and/or hyaluronic acid are assessed regarding material properties and compatibility with cardiomyocyte attachment and function. Microstructure analysis reveals that collagen fiber mats contain a wide range of fiber diameters after crosslinking (from ≈300 nm to ≈5 µm); all other fiber mats contain fibers in the range of ≈120 to ≈300 nm. Fiber mats exhibit comparable electrical conductivity to and greater mechanical properties than the native human myocardium, which is considered beneficial. Cell–matrix interaction analysis utilizing postnatal rat cardiomyocytes reveals that the fiber mats are non-cytotoxic and permit cell attachment and contraction. Fiber mats containing collagen (9.89%), hyaluronic acid (1.1%), and polyaniline (PANi, 1.34%) exhibit the most favorable properties with longer contraction time, higher contractile amplitude, and lower beating rates. Improved contraction is accompanied by increased connexin 43 expression. Importantly, this fiber mat is a suitable material for human-induced pluripotent stem cell–derived cardiomyocytes regarding cytotoxicity, cell attachment, and function. Collectively, these data demonstrate that fiber mats made of collagen, hyaluronic acid, and polyaniline are promising materials for cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-12-31
Keywords: collagen; electroconductive; electrospinning; heart; hyaluronic acid; polyaniline; tissue engineering

Nephronectin Is Required for Vascularization in Zebrafish and Sufficient to Promote Mammalian Vessel-Like Structures in Hydrogels for Tissue Engineering. - Patra, Chinmoy; Rayrikar, Amey; Wagh, Ganesh; Kleefeldt, Florian; Roshanbinfar, Kaveh; Cop, Florian; Nikolic, Iva; Schmidt, Mirko H.H.; Acker-Palmer, Amparo; Ergün, Süleyman; Engel, Felix (Journal of the American Heart Association, 2025)
BACKGROUND: Organs and tissues need to be vascularized during development. Similarly, vascularization is required to engineer thick tissues. How vessels are formed during organogenesis is not fully understood, and vascularization of engineered tissues remains a significant challenge. METHODS AND RESULTS: Here, we show that the extracellular matrix protein nephronectin is required for vascularization during zebrafish development as well as adult fin regeneration and is sufficient to promote mammalian vessel formation and maturation. Nephronectin a morphants and mutants exhibit diminished axial vein sprouting and posterior intersegmental vessel growth. Notably, the angiogenesis-associated integrins itgav and itgb3.1 are coexpressed with nephronectin a in the region of the caudal vein plexus and posterior somites; nephronectin binds to integrin alpha-V/integrin beta-3.1 (ITGAV/ITGB3.1), and itgav morphants phenocopy nephronectin a mutants. In addition, nephronectin a mutants showed decreased vessel maturation compared with wild-type siblings during caudal fin regeneration in adult zebrafish. Moreover, nephronectin promotes mammalian endothelial cell migration and tube formation in 2D and 3-dimensional in vitro tissue culture. Further, nephronectin enhances vascular endothelial growth factor-induced periaortic vascular capillary interconnectivity, vessel diameter, and vessel stability. CONCLUSIONS: Collectively, our results identify nephronectin as a proangiogenic factor during embryonic development, which can be used to improve the vascularization of engineered tissues.
EVALuna2:583978

New functions and signaling mechanisms for the class of adhesion G protein-coupled receptors - Liebscher, Ines; Ackley, Brian; Arac, Demet; Ariestanti, Donna M.; Aust, Gabriela; Bae, Byoung-Il; Bista, Bigyan R.; Bridges, James P.; Duman, Joseph G.; Engel, Felix; Giera, Stefanie; Goffinet, Andre M.; et al. (Annals of the New York Academy of Sciences, 2014)
The class of adhesion G protein-coupled receptors (aGPCRs), with 33 human homologs, is the second largest family of GPCRs. In addition to a seven-transmembrane ?-helix-a structural feature of all GPCRs-the class of aGPCRs is characterized by the presence of a large N-terminal extracellular region. In addition, all aGPCRs but one (GPR123) contain a GPCR autoproteolysis-inducing (GAIN) domain that mediates autoproteolytic cleavage at the GPCR autoproteolysis site motif to generate N- and a C-terminal fragments (NTF and CTF, respectively) during protein maturation. Subsequently, the NTF and CTF are associated noncovalently as a heterodimer at the plasma membrane. While the biological function of the GAIN domain-mediated autocleavage is not fully understood, mounting evidence suggests that the NTF and CTF possess distinct biological activities in addition to their function as a receptor unit. We discuss recent advances in understanding the biological functions, signaling mechanisms, and disease associations of the aGPCRs.
EVALuna2:25477

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

Novel PGS/PCL electrospun fiber mats with patterned topographical features for cardiac patch applications - Tallawi, Marwa; Dippold, Dirk; Rai, Ranjana; D'Atri, D.; Roether, Judith; Schubert, Dirk W.; Rosellini, E.; Engel, Felix; Boccaccini, Aldo R. (Materials Science and Engineering C, 2016)
Nano- and micro-scale topographical features play a critical role in the induction and maintenance of various cellular properties and functions, including morphology, adhesion, gene regulation, and cell-to-cell communication. In addition, recent studies have indicated that the structure and function of heart tissue are also sensitive to mechanical cues at the nano- and micro-scale. Although fabrication methods exist for generating topographical features on polymeric scaffolds for cell culture, current techniques, especially those with nano-scale resolution, are typically complex, prohibitively expensive and not accessible to most biology laboratories. Here, we present a simple and tunable fabrication method for the production of patterned electrospun fibers that simulate the complex anisotropic and multi-scale architecture of cardiac tissue, to promote cardiac cell alignment. This method is based on the combination of electrospinning and soft lithography techniques, in which electrospun fibers, based on a blend of poly(glycerol sebacate) and poly(caprolactone), were collected on a patterned Teflon-coated silicon wafer with imprinted topographical features. Different surface topographies were investigated, such as squares and grooves, with constant or different interspatial distances. In vitro cell culture studies successfully demonstrated the alignment of both C2C12 myoblasts and neonatal rat cardiomyocytes on fabricated electrospun patterned surfaces. C2C12 cells were cultured over a period of 72h to study the effect of topographical cues on cell morphology. Cells attached within the first 8h after seeding and after 24h most of the cells started to align responding to the topographical cues. Similarly, cardiomyocytes responded to the topographical features by aligning themselves and by expressing Connexin 43 along cellular junctions. Summarizing, we have developed a new method with the potential to significantly promote cardiac tissue engineering by fabricating electrospun fibers with defined topographical features to guide and instruct donor and/or host cells.
EVALuna:34665

Novel targets and future strategies for acute cardioprotection: Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart - Hausenloy, Derek J.; Garcia-Dorado, David; Botker, Hans Erik; Davidson, Sean M.; Downey, James; Engel, Felix; Jennings, Robert; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; Ovize, Michel; Perrino, Cinzia; et al. (Cardiovascular Research, 2017)
Ischaemic heart disease and the heart failure that often results, remain the leading causes of death and disability in Europe and worldwide. As such, in order to prevent heart failure and improve clinical outcomes in patients presenting with an acute ST-segment elevation myocardial infarction and patients undergoing coronary artery bypass graft surgery, novel therapies are required to protect the heart against the detrimental effects of acute ischaemia/reperfusion injury (IRI). During the last three decades, a wide variety of ischaemic conditioning strategies and pharmacological treatments have been tested in the clinic-however, their translation from experimental to clinical studies for improving patient outcomes has been both challenging and disappointing. Therefore, in this Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart, we critically analyse the current state of ischaemic conditioning in both the experimental and clinical settings, provide recommendations for improving its translation into the clinical setting, and highlight novel therapeutic targets and new treatment strategies for reducing acute myocardial IRI.
EVALuna2:25533

Novel therapeutic strategies for cardioprotection - Sluijter, Joost P. G.; Condorelli, Gianluigi; Davidson, Sean M.; Engel, Felix; Ferdinandy, Peter; Hausenloy, Derek J.; Lecour, Sandrine; Madonna, Rosalinda; Ovize, Michel; Ruiz-Meana, Marisol; Schulz, Rainer; Van Laake, Linda W. (Pharmacology & Therapeutics, 2014)
The morbidity and mortality from ischemic heart disease (IHD) remain significant worldwide. The treatment for acute myocardial infarction has improved over the past decades, including early reperfusion of occluded coronary arteries. Although it is essential to re-open the artery as soon as possible, paradoxically this leads to additional myocardial injury, called acute ischemia-reperfusion injury (IRI), for which currently no effective therapy is available. Therefore, novel therapeutic strategies are required to protect the heart from acute IRI in order to reduce myocardial infarction size, preserve cardiac function and improve clinical outcomes in patients with IHD. In this review article, we will first outline the pathophysiology of acute IRI and review promising therapeutic strategies for cardioprotection. These include novel aspects of mitochondrial function, epigenetics, circadian clocks, the immune system, microvesicles, growth factors, stem cell therapy and gene therapy. We discuss the therapeutic potential of these novel cardioprotective strategies in terms of pharmacological targeting and clinical application.
EVALuna2:25465

Patient-derived zebrafish xenografts of uveal melanoma reveal ferroptosis as a drug target - Groenewoud, Arwin; Yin, Jie; Gelmi, Maria Chiara; Alsafadi, Samar; Nemati, Fariba; Decaudin, Didier; Roman-Roman, Sergio; Kalirai, Helen; Coupland, Sarah E.; Jochemsen, Aart G.; Jager, Martine J.; Engel, Felix; et al. (Cell Death Discovery, 2023)
Uveal melanoma (UM) has a high risk to progress to metastatic disease with a median survival of 3.9 months after metastases detection, as metastatic UM responds poorly to conventional and targeted chemotherapy and is largely refractory to immunotherapy. Here, we present a patient-derived zebrafish UM xenograft model mimicking metastatic UM. Cells isolated from Xmm66 spheroids derived from metastatic UM patient material were injected into 2 days-old zebrafish larvae resulting in micro-metastases in the liver and caudal hematopoietic tissue. Metastasis formation could be reduced by navitoclax and more efficiently by the combinations navitoclax/everolimus and flavopiridol/quisinostat. We obtained spheroid cultures from 14 metastatic and 10 primary UM tissues, which were used for xenografts with a success rate of 100%. Importantly, the ferroptosis-related genes GPX4 and SLC7A11 are negatively correlated with the survival of UM patients (TCGA: n = 80; Leiden University Medical Centre cohort: n = 64), ferroptosis susceptibility is correlated with loss of BAP1, one of the key prognosticators for metastatic UM, and ferroptosis induction greatly reduced metastasis formation in the UM xenograft model. Collectively, we have established a patient-derived animal model for metastatic UM and identified ferroptosis induction as a possible therapeutic strategy for the treatment of UM patients.
CRIS-Team Scopus Importer:2023-06-30

Persistent scarring and dilated cardiomyopathy suggest incomplete regeneration of the apex resected neonatal mouse myocardium - A 180days follow up study - Andersen, Ditte Caroline; Jensen, Charlotte Harken; Baun, Christina; Hvidsten, Svend; Zebrowski, David; Engel, Felix; Sheikh, Soren Paludan (Journal of Molecular and Cellular Cardiology, 2016)
Heart damage in mammals is generally considered to result in scar formation, whereas zebrafish completely regenerate their hearts following an intermediate and reversible state of fibrosis after apex resection (AR). Recently, using the AR procedure, one-day-old mice were suggested to have full capacity for cardiac regeneration as well. In contrast, using the same mouse model others have shown that the regeneration process is incomplete and that scarring still remains 21days after AR. The present study tested the hypothesis that like in zebrafish, fibrosis in neonatal mammals could be an intermediate response before the onset of complete heart regeneration. Myocardial damage was performed by AR in postnatal day 1 C57BL/6 mice, and myocardial function and scarring assessed at day 180 using F-18-fluorodeoxyglucose positron emission tomography (FDG-PET) and histology, respectively. AR mice exhibited decreased ejection fraction and wall motion with increased end-diastolic and systolic volumes compared to sham-operated mice. Scarring with collagen accumulation was still substantial, with increased heart size, while cardiomyocyte size was unaffected. In conclusion, these data thus show that apex resection in mice results in irreversible fibrosis and dilated cardiomyopathy suggesting that cardiac regeneration is limited in neonatal mammals and thus distinct from the regenerative capacity seen in zebrafish.
EVALuna2:25499

Poly(Glycerol Sebacate)/Poly(Butylene Succinate-Butylene Dilinoleate) Fibrous Scaffolds for Cardiac Tissue Engineering - Tallawi, Marwa; Zebrowski, David; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; El Fray, Miroslawa; Engel, Felix; Aifantis, Katerina E.; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2015)
The present article investigates the use of a novel electrospun fibrous blend of poly(glycerol sebacate) (PGS) and poly(butylene succinate-butylene dilinoleate) (PBS-DLA) as a candidate for cardiac tissue engineering. Random electrospun fibers with various PGS/PBS-DLA compositions (70/30, 60/40, 50/50, and 0/100) were fabricated. To examine the suitability of these fiber blends for heart patches, their morphology, as well as their physical, chemical, and mechanical properties were measured before examining their biocompatibility through cell adhesion. The fabricated fibers were bead-free and exhibited a relatively narrow diameter distribution. The addition of PBS-DLA to PGS resulted in an increase of the average fiber diameter, whereas increasing the amount of PBS-DLA decreased the hydrophilicity and the water uptake of the nanofibrous scaffolds to values that approached those of neat PBS-DLA nanofibers. Moreover, the addition of PBS-DLA significantly increased the elastic modulus. Initial toxicity studies with C2C12 myoblast cells up to 72 h confirmed nontoxic behavior of the blends. Immunofluorescence analyses and scanning electron microscopy analyses confirmed that C2C12 cells showed better cell attachment and proliferation on electrospun mats with higher PBS-DLA content. However, immunofluorescence analyses of the 3-day-old rat cardiomyocytes cultured for 2 and 5 days demonstrated better attachment on the 70/30 fibers containing well-aligned sarcomeres and expressing high amounts of connexin 43 in cellular junctions indicating efficient cell-to-cell communication. It can be concluded, therefore, that fibrous PGS/PBS-DLA scaffolds exhibit promising characteristics as a biomaterial for cardiac patch applications.

Position Paper of the European Society of Cardiology Working Group Cellular Biology of the Heart: cell-based therapies for myocardial repair and regeneration in ischemic heart disease and heart failure - Madonna, Rosalinda; Van Laake, Lindaw.; Davidson, Sean M.; Engel, Felix; Hausenloy, Derek J.; Lecour, Sandrine; Leor, Jonathan; Perrino, Cinzia; Schulz, Rainer; Ytrehus, Kirsti; Landmesser, Ulf; Mummery, Christine L.; et al. (European Heart Journal, 2016)
Despite improvements in modern cardiovascular therapy, the morbidity and mortality of ischaemic heart disease (IHD) and heart failure (HF) remain significant in Europe and worldwide. Patients with IHD may benefit from therapies that would accelerate natural processes of postnatal collateral vessel formation and/or muscle regeneration. Here, we discuss the use of cells in the context of heart repair, and the most relevant results and current limitations from clinical trials using cell-based therapies to treat IHD and HF. We identify and discuss promising potential new therapeutic strategies that include ex vivo cell-mediated gene therapy, the use of biomaterials and cell-free therapies aimed at increasing the success rates of therapy for IHD and HF. The overall aim of this Position Paper of the ESC Working Group Cellular Biology of the Heart is to provide recommendations on how to improve the therapeutic application of cell-based therapies for cardiac regeneration and repair.
EVALuna2:25529

PPARβ/δ: Linking Metabolism to Regeneration - Magadum, Ajit; Engel, Felix (International Journal of Molecular Sciences, 2018)
In contrast to the general belief that regeneration is a rare event, mainly occurring in simple organisms, the ability of regeneration is widely distributed in the animal kingdom. Yet, the efficiency and extent of regeneration varies greatly. Humans can recover from blood loss as well as damage to tissues like bone and liver. Yet damage to the heart and brain cannot be reversed, resulting in scaring. Thus, there is a great interest in understanding the molecular mechanisms of naturally occurring regeneration and to apply this knowledge to repair human organs. During regeneration, injury-activated immune cells induce wound healing, extracellular matrix remodeling, migration, dedifferentiation and/or proliferation with subsequent differentiation of somatic or stem cells. An anti-inflammatory response stops the regenerative process, which ends with tissue remodeling to achieve the original functional state. Notably, many of these processes are associated with enhanced glycolysis. Therefore, peroxisome proliferator-activated receptor (PPAR) β/δ—which is known to be involved for example in lipid catabolism, glucose homeostasis, inflammation, survival, proliferation, differentiation, as well as mammalian regeneration of the skin, bone and liver—appears to be a promising target to promote mammalian regeneration. This review summarizes our current knowledge of PPARβ/δ in processes associated with wound healing and regeneration.
EVALuna2:34819
Keywords: PPAR beta/delta; regeneration; proliferation; differentiation; metabolism; Wnt signaling; PDK1; Akt; glycolysis

Promoting vascularization for tissue engineering constructs: current strategies focusing on HIF-regulating scaffolds - Esser, Tilman; Roshanbinfar, Kaveh; Engel, Felix (Expert Opinion on Biological Therapy, 2018)
INTRODUCTION: Vascularization remains one of the greatest yet unmet challenges in tissue engineering. When engineered tissues are scaled up to therapeutically relevant dimensions, their demand of oxygen and nutrients can no longer be met by diffusion. Thus, there is a need for perfusable vascular structures. Hypoxia-inducible factors (HIF) act as transcriptional oxygen sensors and regulate a multitude of genes involved in adaptive processes to hypoxia, including angiogenesis. Thus, targeting HIFs is a promising strategy to induce vascularization of engineered tissues. Areas covered: Here we review current vascularization strategies and summarize the present knowledge regarding activation of HIF signaling by ions, iron chelating agents, α-Ketoglutarate (αKG) analogues, and the lipid-lowering drug simvastatin to induce angiogenesis. Specifically, we focus on the incorporation of HIF-activating agents into biomaterials and scaffolds for controlled release. Expert opinion: Vascularization of tissue constructs through activation of upstream regulators of angiogenesis offers advantages but also suffers from drawbacks. HIFs can induce a complete angiogenic program; however, this program appears to be too slow to vascularize larger constructs before cell death occurs. It is therefore crucial that HIF-activation is combined with cell protective strategies and prevascularization techniques to obtain fully vascularized, vital tissues of therapeutically relevant dimensions.
EVALuna2:102206

Protease-activated receptor 2 deficient mice develop less angiotensin II induced left ventricular hypertrophy but more cardiac fibrosis. - Meyer zu Schwabedissen, Albrecht; Vergarajauregui, Silvia; Bertog, Marko; Amann, Kerstin Ute; Engel, Felix; Daniel, Christoph (PLoS ONE, 2024)
AIMS: Activation of Protease Activated Receptor 2 (PAR2) has been shown to be involved in regulation of injury-related processes including inflammation, fibrosis and hypertrophy. In this study we will investigate the role of PAR2 in cardiac injury in a mouse model of hypertension using continuous infusion with angiotensin II. METHODS: Hypertension was induced in 12 weeks old wildtype (wt, n = 8) and PAR2 deficient mice (n = 9) by continuous infusion with angiotensin II for 4 weeks using osmotic minipumps. At the end, hearts were collected for analysis of left ventricular hypertrophy (LVH), myocardial capillary supply, fibrosis and localization of PAR2 expression using histological, immunohistological and mRNA expression analysis techniques. In addition, rat cardiac fibroblasts were treated with angiotensin II and PAR2 was inhibited by a blocking antibody and the PAR2 inhibitor AZ3451. RESULTS: Cardiac PAR2 mRNA expression was downregulated by 40±20% in wt mice treated with AngII compared to untreated controls. Four weeks after AngII treatment, LVH was significantly increased in AngII-treated wt mice compared to similarly treated PAR2-deficient animals as determined by relative heart weight, left ventricular cross-sectional area, and analysis of ventricular lumen area determined on sections. Treatment of wt mice resulted in an approximately 3-fold increase in cardiac expression of FGF23, which was 50% lower in PAR2-deficient animals compared to wt animals and therefore no longer significantly different from expression levels in untreated control mice. In contrast, cardiac interstitial fibrosis was significantly higher in PAR2-deficient mice compared to similar treated wt controls, as assessed by Sirius Red staining (>3-fold) and collagen IV staining (>2-fold). Additional experiments with isolated cardiac fibroblasts showed induction of pro-fibrotic genes when treated with PAR2 inhibitors. CONCLUSION: In angiotensin II-induced cardiac injury, PAR2 deficiency has an ambivalent effect, enhancing fibrosis on the one hand, but reducing LVH on the other.
EVALuna2:577005

Pseudo-bipolar spindle formation and cell division in postnatal binucleated cardiomyocytes - Leone, Marina; Engel, Felix (Journal of Molecular and Cellular Cardiology, 2019)
Background: The majority of adult human, mouse and rat cardiomyocytes is not diploid mononucleated. Nevertheless, the current literature on heart regeneration based on cardiomyocyte proliferation focuses mainly on the proliferation capacity of diploid mononucleated cardiomyocytes, instead of the more abundant mononucleated polyploid or binucleated cardiomyocytes. Here, we aimed at a better understanding of the process of mitosis and cell division in postnatal binucleated cardiomyocytes. Methods and results: Postnatal rat binucleated cardiomyocytes were stimulated to re-enter the cell cycle either by fetal bovine serum or a combination of fibroblast growth factor 1 and p38 MAP kinase inhibitor. Phase-contrast videos revealed that binucleated cardiomyocytes form one metaphase plate and preferentially undergo afterwards cytokinesis failure. The maximum rate of cell division of video-recorded binucleated cardiomyocytes was around 6%. Immunofluorescence analyses of centriole number in mitotic binucleated cardiomyocytes revealed that these cells contain more than four centrioles, which can be paired as well as unpaired. In agreement with multiple and/or unpaired centrioles, multipolar spindle formation was observed in mitotic binucleated cardiomyocytes using fluorescence live imaging of tubulin-GFP. Multipoles were transient and resolved into pseudo-bipolar spindles both in case of cell division and cytokinesis failure. Notably, centrioles were in most cases unevenly distributed among daughter cells. Conclusions: Our results indicate that postnatal binucleated cardiomyocytes upon stimulation can enter mitosis, cope with their multiple and/or unpaired centrioles by forming pseudo-bipolar spindles, and divide.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Binucleated cardiomyocyte; Cell division; Centriole; Centrosome; Intermediate multipoles; Live cell imaging

Recombinant spider silk protein eADF4(C16)-RGD coatings are suitable for cardiac tissue engineering - Kramer, Johannes P.M.; Aigner, Tamara B.; Petzold, Jana; Roshanbinfar, Kaveh; Scheibel, Thomas; Engel, Felix (Scientific Reports, 2020)
Cardiac tissue engineering is a promising approach to treat cardiovascular diseases, which are a major socio-economic burden worldwide. An optimal material for cardiac tissue engineering, allowing cardiomyocyte attachment and exhibiting proper immunocompatibility, biocompatibility and mechanical characteristics, has not yet emerged. An additional challenge is to develop a fabrication method that enables the generation of proper hierarchical structures and constructs with a high density of cardiomyocytes for optimal contractility. Thus, there is a focus on identifying suitable materials for cardiac tissue engineering. Here, we investigated the interaction of neonatal rat heart cells with engineered spider silk protein (eADF4(C16)) tagged with the tripeptide arginyl-glycyl-aspartic acid cell adhesion motif RGD, which can be used as coating, but can also be 3D printed. Cardiomyocytes, fibroblasts, and endothelial cells attached well to eADF4(C16)-RGD coatings, which did not induce hypertrophy in cardiomyocytes, but allowed response to hypertrophic as well as proliferative stimuli. Furthermore, Kymograph and MUSCLEMOTION analyses showed proper cardiomyocyte beating characteristics on spider silk coatings, and cardiomyocytes formed compact cell aggregates, exhibiting markedly higher speed of contraction than cardiomyocyte mono-layers on fibronectin. The results suggest that eADF4(C16)-RGD is a promising material for cardiac tissue engineering.
CRIS-Team Scopus Importer:2020-06-09

Silk for cardiac tissue engineering - Engel, Felix (Silk-Based Biomaterials for Tissue Engineering, Regenerative and Precision Medicine, 2023)
Cardiovascular diseases are among the leading causes of death worldwide. In addition, congenital heart disease is the most common congenital disability, affecting almost 1% of newborns. The primary cause of most heart diseases is the irreversible loss of heart muscle cells, the cardiomyocytes. Thus developing novel strategies to prevent, reduce, or reverse cardiomyocyte loss is critically important. One promising strategy to reverse cardiomyocyte loss is cardiac tissue engineering (CTE). This chapter reviews the advances in CTE, the special requirements for heart repair, and the remaining challenges. Subsequently, the suitability of silk for CTE is discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biofabrication; Cardiac tissue engineering (CTE); heart disease; recombinant silk; silk fibroin; vascularization

Single-cell cardiovascular research - Engelhardt, Stefan; Engel, Felix (Cardiovascular Research, 2020)
CRIS-Team Scopus Importer:2020-07-17

Spatially Resolved Genome-wide Transcriptional Profiling Identifies BMP Signaling as Essential Regulator of Zebrafish Cardiomyocyte Regeneration - Wu, Chi-Chung; Kruse, Fabian; Vasudevarao, Mohankrishna Dalvoy; Junker, Jan Philipp; Zebrowski, David; Fischer, Kristin; Noel, Emily S.; Grun, Dominic; Berezikov, Eugene; Engel, Felix; Van Oudenaarden, Alexander; Weidinger, Gilbert; et al. (Developmental Cell, 2016)
In contrast to mammals, zebrafish regenerate heart injuries via proliferation of cardiomyocytes located near the wound border. To identify regulators of cardiomyocyte proliferation, we used spatially resolved RNA sequencing (tomo-seq) and generated a high-resolution genome-wide atlas of gene expression in the regenerating zebrafish heart. Interestingly, we identified two wound border zones with distinct expression profiles, including the re-expression of embryonic cardiac genes and targets of bone morphogenetic protein (BMP) signaling. Endogenous BMP signaling has been reported to be detrimental to mammalian cardiac repair. In contrast, we find that genetic or chemical inhibition of BMP signaling in zebrafish reduces cardiomyocyte dedifferentiation and proliferation, ultimately compromising myocardial regeneration, while bmp2b overexpression is sufficient to enhance it. Our results provide a resource for further studies on the molecular regulation of cardiac regeneration and reveal intriguing differential cellular responses of cardiomyocytes to a conserved signaling pathway in regenerative versus non-regenerative hearts.
EVALuna2:25511

Stem Cell Aging and Age-Related Cardiovascular Disease: Perspectives of Treatment by Ex-vivo Stem Cell Rejuvenation - Madonna, Rosalinda; Engel, Felix; Davidson, Sean M.; Ferdinandy, Peter; Goerbe, Aniko; Sluijter, Joost P. G.; Van Laake, Linda W. (Current Drug Targets, 2015)
Aging affects endogenous stem cells in terms of functionality and numbers. In particular, during aging, the stemness property can decrease because of enhanced apoptotic cell death and senescence. In addition, aging and aging-related co-morbidities affect the paracrine activity of stem cells and the efficiency of their transplantation. Collectively, this leads to a reduction of the capacity of organs to repair themselves, possibly due to a reduced functional capability of stem cells. Therefore, major efforts have been invested to improve the repair capability of stem cells in aged individuals by overexpressing antisenescence and antiapoptotic genes. In this review, we describe critical genes and signaling pathways in stem cell aging and discuss ex vivo genetic modification approaches aimed at stem cell rejuvenation that are of interest for the cardiovascular system.
EVALuna2:25484

Stem Cells and Their Cardiac Derivatives for Cardiac Tissue Engineering and Regenerative Medicine - Roshanbinfar, Kaveh; Esser, Tilman; Engel, Felix (Antioxidants & Redox Signaling, 2020)
Significance: Heart failure is among the leading causes of morbidity worldwide with a 5-year mortality rate of similar to 50%. Therefore, major efforts are invested to reduce heart damage upon injury or maintain and at best restore heart function.
CRIS-Team WoS Importer:2020-12-04

Structural and geochemical assessment of the coralline alga Tethysphytum antarcticum from Terra Nova Bay, Ross Sea, Antarctica - López Correa, Matthias; Teichert, Sebastian; Ragazzola, Federica; Cazorla Vázquez, Salvador; Engel, Felix; Hurle, Katrin; Mazzoli, Claudio; Kuklinski, Piotr; Raiteri, Giancarlo; Lombardi, Chiara (Minerals, 2023)
Crustose coralline algae (CCA) occur from the tropics to the poles in photic benthic environments. Here, we report on some of the world’s southernmost and coldest CCA sites in Terra Nova, Ross Sea, Antarctica at 74°41′ S. The recently described red alga Tethysphytum antarticum is investigated for its skeletal architecture, its mineralogical and geochemical composition, as well as for its taxonomic classification. A phylogenetic analysis based on molecular genetics and the sequencing of the photosystem II protein D1 (psbA) gave a perfect match with T. antarcticum. Histological sections and micro-CT-scans provide new diagnostic details for the conceptacles (the reproductive organs of the alga). X-ray diffractometry and electron-microprobe measurements yielded a clear high-Mg calcite ( 8 mol%) composition of the skeletal parts. Detailed back-scattered electron imaging of polished petrographic thin sections revealed a two-layered thallus (vegetative plant tissue), comprising an organic-rich irregularly calcified basal layer with rectangular cells, overlain by the main thallus. Elemental maps show relatively increased sulphur in the basal layer, clearly tied to organic cell walls. MgCO3 and SrCO3 were targeted with semiquantitative elemental mappings and in an ontogenetic quantitative spot transect. Compared with temperature (−1.95 °C to +1.08 °C), the MgCO3 (mol%) reflects this world’s coldest CCA site temperature with the lowest MgCO3 content of 7.9 ± 1.6 mol%. The along transect variability, however, shows with 6 mol% a larger MgCO3 variability than expected for the 3 °C intra-annual temperature amplitude in Terra Nova Bay. This implies that in low amplitude settings the biomineralisation control on Mg/Ca ratios can outcompete its temperature sensitivity. Mark-recapture studies, next to the environmental logger station La Zecca are suggested, to perform a detailed growth rate and biomineralisation quantificatio
Keywords: crustose coralline algae; Antarctica; taxonomy; phylogeny; thallus structure; biomineralization; geochemistry; climate change

Surface Features of Recombinant Spider Silk Protein eADF4(kappa 16)-Made Materials are Well-Suited for Cardiac Tissue Engineering - Petzold, Jana; Aigner, Tamara B.; Touska, Filip; Zimmermann, Katharina; Scheibel, Thomas; Engel, Felix (Advanced Functional Materials, 2017)
Cardiovascular diseases causing high morbidity and mortality represent a major socioeconomic burden. The primary cause of impaired heart function is often the loss of cardiomyocytes. Thus, novel therapies aim at restoring the lost myocardial tissue. One promising approach is cardiac tissue engineering. Previously, it is shown that Antheraea mylitta silk protein fibroin is a suitable material for cardiac tissue engineering, however, its quality is difficult to control. To overcome this limitation, the interaction of primary rat heart cells with engineered Araneus diadematus fibroin 4 (kappa 16) (eADF4(kappa 16)) is investigated here, which is engineered based on the sequence of ADF4 by replacing the glutamic acid residue in the repetitive unit of its core domain with lysine. The data demonstrate that cardiomyocytes, fibroblasts, endothelial cells, and smooth muscle cells attach well to eADF4(kappa 16) films on glass coverslips which provide an engineered surface with a polycationic character. Moreover, eADF4(kappa 16) films have, in contrast to fibronectin films, no hypertrophic effect but allow the induction of cardiomyocyte hypertrophy. Finally, cardiomyocytes grown on eADF4(kappa 16) films respond to pro-proliferative factors and exhibit proper cell-to-cell communication and electric coupling. Collectively, these data demonstrate that designed recombinant eADF4(kappa 16)-based materials are promising materials for cardiac tissue engineering.
EVALuna2:34287
Keywords: adhesion; cardiac tissue engineering; cell-material interactions; eADF4(kappa 16); engineered spider silk proteins

The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

The endocardial expression of ADGRG6 (Gpr126) is necessary for survival in mouse and sufficient to drive trabeculation in zebrafish - Musa, Gentian; Srivastava, S.; Engel, Felix (2018)
EVALuna2:34443

The expanding functional roles and signaling mechanisms of adhesion G protein–coupled receptors - Morgan, Rory K.; Anderson, Garret R.; Araç, Demet; Aust, Gabriela; Balenga, Nariman; Boucard, Antony; Bridges, James P.; Engel, Felix; Formstone, Caroline J.; Glitsch, Maike D.; Gray, Ryan S.; Hall, Randy A.; et al. (Annals of the New York Academy of Sciences, 2019)
The adhesion class of G protein–coupled receptors (GPCRs) is the second largest family of GPCRs (33 members in humans). Adhesion GPCRs (aGPCRs) are defined by a large extracellular N-terminal region that is linked to a C-terminal seven transmembrane (7TM) domain via a GPCR-autoproteolysis inducing (GAIN) domain containing a GPCR proteolytic site (GPS). Most aGPCRs undergo autoproteolysis at the GPS motif, but the cleaved fragments stay closely associated, with the N-terminal fragment (NTF) bound to the 7TM of the C-terminal fragment (CTF). The NTFs of most aGPCRs contain domains known to be involved in cell–cell adhesion, while the CTFs are involved in classical G protein signaling, as well as other intracellular signaling. In this workshop report, we review the most recent findings on the biology, signaling mechanisms, and physiological functions of aGPCRs.
CRIS-Team Scopus Importer:2019-06-28
Keywords: adhesion G protein–coupled receptor; cancer; development; immunology; mechanosensation; neurobiology; signal transduction; structural biology

The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin

The multiple signaling modalities of adhesion G protein-coupled receptor GPR126 in development - Patra, Chinmoy; Monk, Kelly R.; Engel, Felix (Receptors & Clinical Investigation, 2014)
The G protein-coupled receptor (GPCR) superfamily is the largest known receptor family in the human genome. Although the family of adhesion GPCRs comprises the second largest sub-family, their function is poorly understood. Here, we review the current knowledge about the adhesion GPCR family member GPR126. GPR126 possesses a signal peptide, a 7TM domain homologous to secretin-like GPCRs, a GPS motif and an extended N-terminus containing a CUB (Complement, Uegf, Bmp1) domain, a PTX (Pentraxin) domain, a hormone binding domain and 27 putative N-glycosylation sites. Knockdown and knockout experiments in zebrafish and mice have demonstrated that Gpr126 plays an essential role in neural, cardiac and ear development. In addition, genome-wide association studies have implicated variations at the GPR126 locus in obstructive pulmonary dysfunction, in scoliosis and as a determinant of trunk length and body height. Gpr126 appears to exert its function depending on the organ system via G protein- and/or N-terminus-dependent signaling. Here, we review the current knowledge about Gpr126, which, due to the variety of its functions and its multiple signaling modalities, provides a model adhesion GPCR to understand general functional concepts utilized by adhesion GPCRs.
EVALuna2:25482

Towards regenerating the mammalian heart: challenges in evaluating experimentally induced adult mammalian cardiomyocyte proliferation - Zebrowski, David; Becker, Robert; Engel, Felix (American Journal of Physiology-Heart and Circulatory Physiology, 2016)
In recent years, there has been a dramatic increase in research aimed at regenerating the mammalian heart by promoting endogenous cardiomyocyte proliferation. Despite many encouraging successes, it remains unclear if we are any closer to achieving levels of mammalian cardiomyocyte proliferation for regeneration as seen during zebrafish regeneration. Furthermore, current cardiac regenerative approaches do not clarify whether the induced cardiomyocyte proliferation is an epiphenomena or responsible for the observed improvement in cardiac function. Moreover, due to the lack of standardized protocols to determine cardiomyocyte proliferation in vivo, it remains unclear if one mammalian regenerative factor is more effective than another. Here, we discuss current methods to identify and evaluate factors for the induction of cardiomyocyte proliferation and challenges therein. Addressing challenges in evaluating adult cardiomyocyte proliferation will assist in determining 1) which regenerative factors should be pursued in large animal studies; 2) if a particular level of cell cycle regulation presents a better therapeutic target than another (e.g., mitogenic receptors vs. cyclins); and 3) which combinatorial approaches offer the greatest likelihood of success. As more and more regenerative studies come to pass, progress will require a system that not only can evaluate efficacy in an objective manner but can also consolidate observations in a meaningful way.
EVALuna2:25528

TWEAK-Fn14 Cytokine-Receptor Axis: A New Player of Myocardial Remodeling and Cardiac Failure - Novoyatleva, Tatyana; Sajjad, Amna; Engel, Felix (Frontiers in Immunology, 2014)
Tumor necrosis factor (TNF) has been firmly established as a pathogenic factor in heart failure, a significant socio-economic burden. In this review, we will explore the role of other members of the TNF/TNF receptor superfamily (TNFSF/TNFRSF) in cardiovascular diseases (CVDs) focusing on TWEAK and its receptor Fn14, new players in myocardial remodeling and heart failure. The TWEAK/Fn14 pathway controls a variety of cellular activities such as proliferation, differentiation, and apoptosis and has diverse biological functions in pathological mechanisms like inflammation and fibrosis that are associated with CVDs. Furthermore, it has recently been shown that the TWEAK/Fn14 axis is a positive regulator of cardiac hypertrophy and that deletion of Fn14 receptor protects from right heart fibrosis and dysfunction. We discuss the potential use of the TWEAK/Fn14 axis as biomarker for CVDs as well as therapeutic target for future treatment of human heart failure based on supporting data from animal models and in vitro studies. Collectively, existing data strongly suggest the TWEAK/Fn14 axis as a potential new therapeutic target for achieving cardiac protection in patients with CVDs.
EVALuna2:25479

Vascularisation for cardiac tissue engineering: the extracellular matrix - Patra, Chinmoy; Boccaccini, Aldo R.; Engel, Felix (Thrombosis and Haemostasis, 2015)
Cardiovascular diseases present a major socio-economic burden. One major problem underlying most cardiovascular and congenital heart diseases is the irreversible loss of contractile heart muscle cells, the cardiomyocytes. To reverse damage incurred by myocardial infarction or by surgical correction of cardiac malformations, the loss of cardiac tissue with a thickness of a few millimetres needs to be compensated. A promising approach to this issue is cardiac tissue engineering. In this review we focus on the problem of in vitro vascularisation as implantation of cardiac patches consisting of more than three layers of cardiomyocytes (>100 mu m thick) already results in necrosis. We explain the need for vascularisation and elaborate on the importance to include non-myocytes in order to generate functional vascularised cardiac tissue. We discuss the potential of extracellular matrix molecules in promoting vascularisation and introduce nephronectin as an, example of a new promising candidate. Finally, we discuss current biomaterial-based approaches including micropatterning, electrospinning, 3D micro-manufacturing technology and porogens. Collectively, the current literature supports the notion that cardiac tissue engineering is a realistic option for future treatment of paediatric and adult patients with cardiac disease.
Keywords: Heart; vascularisation; coronary vasculature; tissue engineering; extracellular matrix

Zeb1 mediates EMT/plasticity-associated ferroptosis sensitivity in cancer cells by regulating lipogenic enzyme expression and phospholipid composition - Schwab, Annemarie; Rao, Zhigang; Zhang, Jie; Gollowitzer, André; Siebenkäs, Katharina; Bindel, Nino; D’Avanzo, Elisabetta; van Roey, Ruthger; Hajjaj, Yussuf; Özel, Ece; Armstark, Isabell; Bereuter, Leonhard; et al. (Nature Cell Biology, 2024)
Therapy resistance and metastasis, the most fatal steps in cancer, are often triggered by a (partial) activation of the epithelial–mesenchymal transition (EMT) programme. A mesenchymal phenotype predisposes to ferroptosis, a cell death pathway exerted by an iron and oxygen-radical-mediated peroxidation of phospholipids containing polyunsaturated fatty acids. We here show that various forms of EMT activation, including TGFβ stimulation and acquired therapy resistance, increase ferroptosis susceptibility in cancer cells, which depends on the EMT transcription factor Zeb1. We demonstrate that Zeb1 increases the ratio of phospholipids containing pro-ferroptotic polyunsaturated fatty acids over cyto-protective monounsaturated fatty acids by modulating the differential expression of the underlying crucial enzymes stearoyl-Co-A desaturase 1 (SCD), fatty acid synthase (FASN), fatty acid desaturase 2 (FADS2), elongation of very long-chain fatty acid 5 (ELOVL5) and long-chain acyl-CoA synthetase 4 (ACSL4). Pharmacological inhibition of selected lipogenic enzymes (SCD and FADS2) allows the manipulation of ferroptosis sensitivity preferentially in high-Zeb1-expressing cancer cells. Our data are of potential translational relevance and suggest a combination of ferroptosis activators and SCD inhibitors for the treatment of aggressive cancers expressing high Zeb1.
CRIS-Team Scopus Importer:2024-08-02